Thermoplastic polymer foamed particle, thermoplastic polymer foamed particle molded body, and identification method of thermoplastic polymer foamed particle or thermoplastic polymer foamed particle molded body
By utilizing thermoplastic polymer foamed particles that exhibit a luminescence reaction upon electromagnetic irradiation, the challenges of identifying and distinguishing foamed particles are addressed, ensuring aesthetic preservation and secure tracking of source information.
Patent Information
- Application Number
- JP2023161733
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2025-04-07
AI Technical Summary
Existing technologies face challenges in identifying molded foamed particles and distinguishing the foamed particles used in their manufacture, which affects aesthetics and sales destinations. Additionally, physically marking foamed particles is costly and requires special equipment.
The use of thermoplastic polymer foamed particles that exhibit a luminescence reaction derived from a luminescent rare earth element when irradiated with electromagnetic waves, allowing for identification through detection of this reaction. This method includes a first identification method comparing the emission spectrum with a blank spectrum and a second method matching the emission spectrum with a preset reference spectrum.
This solution enables the distinct identification of thermoplastic polymer foamed particles and molded articles without compromising their aesthetic appearance, allowing for tracking of the source information of the foamed particles. The luminescence reaction provides a unique and secure method of identification.
Smart Images

Figure 2025052817000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an identifiable expanded thermoplastic polymer bead, an expanded thermoplastic polymer bead molding, and a method for identifying expanded thermoplastic polymer beads or expanded thermoplastic polymer bead moldings. [Background technology]
[0002] 2. Description of the Related Art Conventionally, from the viewpoints of preventing counterfeiting, managing products, managing production history, and the like, techniques have been proposed for attaching identification information to products to make them identifiable.
[0003] As a technique for providing identification information to a resin molded product, for example, Patent Document 1 discloses a technique for providing a predetermined index on the surface of a foamed resin molded product by utilizing the tip surface of a piston that closes a cavity in a raw material filling machine for foamed resin molding. Patent Document 2 discloses a technique for irradiating a laser onto the surface of a molded product obtained by molding a resin composition to partially foam the product, thereby forming a foamed identification part and marking the product. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2010-149297 (Sekisui Plastics) [Patent Document 2] WO2022 / 191310A1 (Asahi Kasei) Summary of the Invention [Problem to be solved by the invention]
[0005] However, there are problems in identifying expanded bead moldings formed using expanded beads. In the conventional technology, a visually identifiable identification mark is attached to the surface of the molding, so that the identification mark stands out in appearance, which is problematic from the viewpoint of aesthetics. This sometimes results in limitations on the applications and sales destinations of the moldings. Furthermore, the above-mentioned conventional technique of providing an identification mark on the surface of a molded product makes it possible to identify the expanded bead molding itself, but it is not possible to identify what type of expanded beads were used to produce the expanded bead molding.
[0006] For example, there are cases where the manufacturer of the expanded beads is different from the manufacturer that purchases the expanded beads and manufactures the expanded bead moldings, and in such cases, it is difficult for the user of the expanded bead moldings to distinguish whether the expanded bead moldings have been manufactured using the expanded beads that he or she desires.
[0007] On the other hand, physically marking the surface of the expanded beads in order to make the expanded beads themselves identifiable would require special manufacturing equipment, which would be costly and therefore unrealistic.
[0008] The present invention has been made in consideration of the above problems. That is, the present invention proposes a technology that makes it possible to distinguish the expanded thermoplastic polymer beads themselves and to distinguish the expanded thermoplastic polymer beads moldings without impairing the aesthetic appearance by being composed of identifiable expanded thermoplastic polymer beads. [Means for solving the problem]
[0009] The expanded thermoplastic polymer particles of the present invention are characterized in that they exhibit a luminescent reaction derived from a luminescent rare earth element when irradiated with electromagnetic waves.
[0010] The expanded thermoplastic polymer bead molding of the present invention is characterized in that it is produced by molding the expanded thermoplastic polymer bead of the present invention in a mold.
[0011] The method for identifying the expanded thermoplastic polymer beads or the expanded thermoplastic polymer bead molding of the present invention includes at least one of the following first and second identification methods. That is, the first identification method is characterized by including: i) an electromagnetic wave irradiation step of irradiating electromagnetic waves to the surface of a thermoplastic polymer foamed particle or a thermoplastic polymer foamed particle molding; ii) a detection step of detecting, with a detection device, a luminescence reaction originating from a luminescent rare earth element caused by the electromagnetic wave irradiation, and obtaining an emission spectrum; and iii-1) an identification step of comparing the emission spectrum with a blank spectrum that does not show a luminescence reaction originating from a luminescent rare earth element.
[0012] The second identification method is characterized by comprising: i) an electromagnetic wave irradiation step of irradiating electromagnetic waves onto the surface of a thermoplastic polymer foamed particle or a thermoplastic polymer foamed particle molding; ii) a detection step of detecting a luminescence reaction originating from a luminescent rare earth element caused by the electromagnetic wave irradiation using a detection device to obtain an emission spectrum; and iii-2) an identification step of comparing the emission spectrum with a predetermined reference emission spectrum that shows a luminescence reaction originating from a luminescent rare earth element. Effect of the Invention
[0013] The expanded thermoplastic polymer particles of the present invention exhibit a luminescence reaction derived from a luminescent rare earth element when irradiated with electromagnetic waves, and therefore the expanded thermoplastic polymer particles of the present invention can be identified by detecting the luminescence reaction. In addition, the thermoplastic polymer expanded bead molding obtained by molding the thermoplastic polymer expanded beads of the present invention in a mold is composed of expanded beads exhibiting the above-mentioned luminescent reaction. Therefore, the thermoplastic polymer expanded bead molding of the present invention exhibits a luminescent reaction derived from a luminescent rare earth element when irradiated with electromagnetic waves. By detecting the above-mentioned luminescent reaction, the thermoplastic polymer expanded bead molding can be identified, and it can also be identified that the thermoplastic polymer expanded bead molding is composed of the thermoplastic polymer expanded beads of the present invention. In addition, the first identification method of the present invention makes it possible to identify the thermoplastic polymer foamed beads or thermoplastic polymer foamed bead moldings of the present invention by comparing the emission spectrum detected in the luminescence reaction derived from the luminescent rare earth element in the thermoplastic polymer foamed beads or thermoplastic polymer foamed bead moldings with a blank spectrum that does not show a luminescence reaction derived from the luminescent rare earth element. In addition, the second identification method of the present invention can identify whether the thermoplastic polymer foamed beads or thermoplastic polymer foamed bead moldings of the present invention are the specified thermoplastic polymer foamed beads or specified thermoplastic polymer foamed bead moldings by comparing the emission spectrum detected in the luminescence reaction derived from the luminescent rare earth element in the thermoplastic polymer foamed beads or thermoplastic polymer foamed bead moldings with a predetermined reference emission spectrum showing the luminescence reaction derived from the luminescent rare earth element. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a schematic cross-sectional view of a single-layer type thermoplastic polymer foam bead according to one embodiment of the present invention. [Diagram 2] FIG. 1 is a schematic cross-sectional view of a two-layer type thermoplastic polymer foam bead according to one embodiment of the present invention. [Diagram 3] FIG. 1 is a schematic cross-sectional view of a three-layer type thermoplastic polymer foam bead according to one embodiment of the present invention. [Figure 4] FIG. 1 is a schematic cross-sectional view along the axial direction of a two-layer cylindrical type thermoplastic polymer foam bead, which is one embodiment of the present invention. [Diagram 5] 1 is a chart showing the emission spectrum of the light-emitting compound 1 used in the examples. [Figure 6] 1 is a chart showing the emission spectrum of the expanded bead molding of Example 1 and the spectrum (baseline) of a blank expanded bead molding. [Figure 7] FIG. 2 is a schematic diagram of a DSC curve measured to obtain the total heat of fusion and the high-temperature peak heat of the expanded polyolefin resin beads according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The following describes the thermoplastic polymer expanded beads of the present invention (hereinafter sometimes referred to as the expanded beads or expanded beads of the present invention), the thermoplastic polymer expanded bead molding of the present invention (hereinafter sometimes referred to as the expanded bead molding or molding of the present invention), and the method for identifying the thermoplastic polymer expanded beads or thermoplastic polymer expanded bead molding of the present invention (hereinafter sometimes simply referred to as the identification method of the present invention or identification method).
[0016] In the description of the present invention, the emission spectrum, the inherent emission spectrum of a luminescent rare earth element component, the blank spectrum not showing a luminescent reaction derived from a luminescent rare earth element, and the predetermined reference emission spectrum showing a luminescent reaction derived from a luminescent rare earth element respectively refer to the following:
[0017] The emission spectrum means the emission spectrum of the luminescence reaction caused by irradiating the measurement object with electromagnetic waves of a specific wavelength. The measurement object includes molded products such as expanded beads and expanded bead moldings, and the luminescent rare earth element component itself. In the present invention, the emission spectrum is a concept composed of elements such as the shape of the entire pattern, the number of peaks, the wavelength at which each peak is detected, the shape of each peak, the intensity ratio between each peak, and the area ratio between each peak. The wavelength of the light emitted in the luminescence reaction is not particularly limited, and examples thereof include visible light and infrared light.
[0018] The inherent emission spectrum of a luminescent rare earth element component refers to the emission spectrum detected when the luminescent rare earth element component itself is irradiated with electromagnetic waves of a specific wavelength. The inherent emission spectrum differs depending on the type and combination of the luminescent rare earth elements selected. Therefore, it is possible to cause a luminescence reaction that shows a different inherent emission spectrum by using a specific luminescent rare earth element or a combination of two or more luminescent rare earth elements. In this specification, the inherent emission spectrum of a luminescent rare earth element component may be simply referred to as an inherent emission spectrum.
[0019] The blank spectrum not showing a luminescent reaction derived from a luminescent rare earth element refers to a spectrum detected when an electromagnetic wave of a predetermined wavelength is irradiated to a molded product that does not contain a luminescent rare earth element component and is composed of a polymer of a predetermined composition. The molded product may be an expanded bead or an expanded bead molding. The blank spectrum not showing a luminescent reaction derived from a luminescent rare earth element is specifically a spectrum detected when an electromagnetic wave of a predetermined wavelength is irradiated to a molded product composed of a polymer having the same composition as the expanded bead or expanded bead molding to be identified except that it does not contain a luminescent rare earth element component. In addition, the molded product may be an expanded bead or an expanded bead molding manufactured by the same manufacturing method as the expanded bead or expanded bead molding to be identified. In this specification, the blank spectrum not showing a luminescent reaction derived from the luminescent rare earth element may be simply referred to as a blank spectrum. The blank spectrum is used in the first identification method described later.
[0020] The predetermined reference emission spectrum showing the luminescence reaction derived from the luminescent rare earth element refers to an emission spectrum detected when an electromagnetic wave of a predetermined wavelength is irradiated to a molded article containing a predetermined luminescent rare earth element component and composed of a polymer of a predetermined composition. The emission spectrum shows a luminescence reaction derived from the luminescent rare earth element. The molded article may be an expanded bead or an expanded bead molding. The content of the luminescent rare earth element component in the expanded bead used to obtain the reference emission spectrum can be approximately 0.0001 mass% or more and 0.5 mass% or less. In this specification, the predetermined reference emission spectrum showing the luminescence reaction derived from the luminescent rare earth element may be simply referred to as a reference emission spectrum or a predetermined reference emission spectrum. The reference emission spectrum is used in the second identification method described later. In the following, a process of detecting the reference emission spectrum by irradiating an electromagnetic wave of a predetermined wavelength to an expanded bead containing a predetermined luminescent rare earth element component and composed of a polymer of a predetermined composition may be described. This step can also be carried out in the same manner by using an expanded bead molding made of the expanded beads instead of the expanded beads used for the detection.
[0021] [Thermoplastic polymer foam particles] The expanded beads of the present invention are expanded thermoplastic polymer beads that exhibit a luminescence reaction derived from a luminescent rare earth element when irradiated with electromagnetic waves. Specifically, the expanded beads exhibit a luminescence reaction that can be detected as an emission spectrum when irradiated with electromagnetic waves. The present invention is completely different from the conventional technology of physically marking the expanded bead molding, and imparts identifiability by luminescence reaction to the expanded beads themselves that constitute the expanded bead molding. Therefore, the present invention does not impair the aesthetic appearance of the expanded bead molding itself. In addition, the identification method described below is possible. The spectrum of the luminescence reaction derived from the luminescent rare earth element varies depending on the type and combination of the luminescent rare earth elements contained in the expanded beads, and the composition of the polymer that constitutes the expanded beads. Therefore, for example, according to the second identification method described below, by comparing whether or not a preset reference emission spectrum and an emission spectrum detected from the expanded beads to be identified show a similar pattern, the expanded beads can be identified more precisely. Furthermore, when an expanded bead molding produced by in-mold molding using the expanded beads of the present invention is irradiated with electromagnetic waves, the expanded beads of the present invention constituting the expanded bead molding show a light-emitting reaction. By detecting such a light-emitting reaction, the expanded bead molding is identified as being made using the expanded beads of the present invention. Therefore, according to the present invention, it is possible to trace the expanded beads constituting the expanded bead molding from the expanded bead molding. In other words, according to the present invention, it is possible to ascertain, from the expanded bead molding, the source information, etc. of the expanded beads constituting the expanded bead molding. The source information, etc. is information linked to a preset reference emission spectrum, and will be described in detail later.
[0022] The expanded beads of the present invention will be described in more detail below. In the following description, preferred numerical ranges of the present invention may be indicated as appropriate.
[0023] (Thermoplastic polymer) The expanded beads of the present invention are comprised of a thermoplastic polymer. The thermoplastic polymer refers to a polymer having thermoplastic properties, and specifically includes a thermoplastic resin and a thermoplastic elastomer.
[0024] Examples of the thermoplastic resin include polyolefin resins such as polypropylene resins and polyethylene resins; polystyrene resins; polyamide resins; polyester resins; polycarbonate resins; and modified polyphenylene ether resins.
[0025] In this specification, the polypropylene-based resin refers to a propylene homopolymer and a polypropylene-based copolymer containing 50% by mass or more of a structural unit derived from propylene.Specific examples include propylene homopolymers such as isotactic polypropylene, syndiotactic polypropylene, and atactic polypropylene; propylene-based copolymers such as ethylene-propylene copolymer, butene-propylene copolymer, hexene-propylene copolymer, ethylene-propylene-butene terpolymer, and propylene-maleic anhydride copolymer.These copolymers may be, for example, random copolymers or block copolymers, but are preferably random copolymers.
[0026] In this specification, the polyethylene resin refers to an ethylene homopolymer and an ethylene copolymer containing 50% by mass or more of a structural unit derived from ethylene. Specific examples include polyethylenes such as high-density polyethylene (PE-HD), medium-density polyethylene (PE-MD), low-density polyethylene (PE-LD), linear low-density polyethylene (PE-LLD), and linear very low-density polyethylene; and ethylene copolymers such as ethylene-vinyl acetate copolymer and ethylene-methyl methacrylate copolymer.
[0027] In this specification, the polyamide resin refers to a resin having an amide bond in the molecular chain.Specific examples of the polyamide resin include homopolyamides such as nylon 6 obtained by ring-opening polymerization of ε-caprolactam, nylon 66 obtained by co-condensation polymerization of hexamethylenediamine and adipic acid, and polyamide copolymers such as polycaproamide / polyhexamethyleneadipamide copolymer (nylon 6 / 66), caprolactam / hexamethylenediaminoadipic acid / lauryllactam (nylon 6 / 66 / 12), and caprolactam / lauryllactam copolymer (nylon 6 / 12).
[0028] In this specification, the polyester resin refers to a resin having an ester bond in the molecular chain. Specific examples of the polyester resin include aliphatic polyesters such as polylactic acid, polybutylene succinate, polybutylene adipate, and polyhydroxybutyric acid, and aromatic polyesters such as polyethylene terephthalate and polybutylene terephthalate.
[0029] Examples of the thermoplastic elastomer include olefin-based thermoplastic elastomers (TPO); urethane-based thermoplastic elastomers (TPU); and the like.
[0030] In addition, a person skilled in the art can distinguish between thermoplastic resins and thermoplastic elastomers. Thermoplastic resins usually have a flexural modulus of 100 MPa or more. From the viewpoint of moldability of the expanded beads, the flexural modulus of the thermoplastic resin is preferably 3000 MPa or less, more preferably 2000 MPa or less, even more preferably 1500 MPa or less, and particularly preferably 1200 MPa or less. On the other hand, thermoplastic elastomers exhibit rubber elasticity at room temperature and usually have a flexural modulus of less than 100 MPa. In addition, the flexural modulus of the thermoplastic polymer can be determined based on JIS K7171:2008. From the viewpoint of excellent balance between moldability and physical properties of the expanded beads, it is preferable that the expanded beads of the present invention are composed of a thermoplastic resin.
[0031] The expanded beads of the present invention may be composed of one type of thermoplastic polymer, or may be composed of two or more types of thermoplastic polymers.
[0032] From the viewpoint of obtaining better shock-absorbing properties, compression recovery and light weight of the foamed bead molding obtained by in-mold molding using the foamed beads of the present invention, the foamed beads of the present invention preferably contain a polyolefin resin, more preferably a polypropylene resin. In 100% by mass of the thermoplastic polymer constituting the foamed beads of the present invention, the polypropylene resin is preferably contained in an amount of 70% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more.
[0033] From the viewpoint of the Sustainable Development Goals (SDGs), the expanded beads of the present invention preferably contain a thermoplastic polymer derived from recycling. Here, the term "thermoplastic polymer derived from recycling" broadly includes thermoplastic polymers recovered from waste materials generated at production sites during production and waste products such as used films and foamed molded articles.
[0034] In recent years, there has been a social trend to provide products using recycled materials. Therefore, those who provide final products to the market may wish to indicate that at least a portion of the product contains recycled materials. However, in the technical field of expanded bead moldings, the manufacturer of the expanded beads may be different from the manufacturer who purchases the expanded beads and manufactures the expanded bead moldings. In such cases, there is a problem that it is difficult for the purchaser (e.g., user) of the expanded bead molding to confirm whether the expanded beads constituting the expanded bead molding are expanded beads containing a thermoplastic polymer derived from recycling.
[0035] In contrast, in the expanded beads of the present invention containing a recycled thermoplastic polymer, the expanded beads themselves or an expanded bead molding made using the expanded beads exhibits a luminous reaction derived from a luminescent rare earth when irradiated with electromagnetic waves. Therefore, users of the expanded bead moldings should be aware in advance of the information that the expanded beads containing the recycled thermoplastic polymer, which is the material used, exhibit a predetermined luminous reaction when irradiated with electromagnetic waves. This allows the users to identify that the expanded bead moldings they have obtained have been manufactured using expanded beads containing a recycled thermoplastic polymer by irradiating the expanded bead moldings with electromagnetic waves and detecting the luminous reaction. In other words, the above-mentioned embodiment of the present invention makes it possible to trace the expanded beads containing the recycled thermoplastic polymer.
[0036] Recycled thermoplastic polymers include, for example, thermoplastic polymers derived from recycled materials such as post-consumer materials and pre-consumer materials. Post-consumer materials, as defined in JIS Q14021:2000, refer to materials discharged from households, or materials generated as products that can no longer be used for their original purpose by commercial, industrial, and various facilities that are end users of products, including materials returned from distribution channels. Pre-consumer materials, as defined in JIS Q14021:2000, refer to materials removed from the waste stream in the manufacturing process, excluding products that cannot be processed, cannot be polished, scrap, etc. that can be reused in the same process as the generation of the materials. In this specification, recycled materials also include products that cannot be processed, cannot be polished, scrap, etc. that can be reused in the same process as the generation of the pre-consumer materials. Thermoplastic polymers derived from these recycled materials can generally be obtained by collecting these recycled materials, crushing and / or melting them, and pelletizing them. For example, thermoplastic resins derived from post-consumer materials can be obtained by collecting used thermoplastic resin foam molded articles used by end users, crushing and / or melting them, and pelletizing them. Thermoplastic resins derived from post-consumer materials can also be obtained by collecting thermoplastic resins from automobile shredder residue (also called ASR) generated during the disposal of automobiles, crushing and / or melting them, and pelletizing them. In the present invention, the expanded beads containing recycled thermoplastic polymers may be composed only of the above-mentioned recycled thermoplastic polymers, or may be composed of a mixture of recycled thermoplastic polymers and virgin thermoplastic polymers. In this specification, virgin thermoplastic polymers refer to new thermoplastic polymers excluding recycled materials. The recycled thermoplastic polymer may be the same as the thermoplastic polymer described above, except that it is recycled.
[0037] When the expanded beads of the present invention are composed of a mixture of a virgin thermoplastic polymer and a recycled thermoplastic polymer, the mass ratio of the virgin thermoplastic polymer to the recycled thermoplastic polymer in the expanded beads (virgin thermoplastic polymer:recycled thermoplastic polymer) is preferably 97:3 to 1:99, more preferably 95:5 to 10:90, even more preferably 90:10 to 30:70, and particularly preferably 85:15 to 50:50.
[0038] The expanded beads of the present invention may contain other polymers other than the thermoplastic polymer. Examples of other polymers include thermosetting resins and rubbers. The content of other polymers in the expanded beads is preferably 20% by mass or less, more preferably 10% by mass or less, even more preferably 5% by mass or less, particularly preferably 3% by mass or less, and most preferably 0, that is, the expanded beads substantially contain only thermoplastic polymers as polymers.
[0039] (Luminescent rare earth elements) The expanded beads of the present invention show a luminescence reaction derived from a luminescent rare earth element when irradiated with electromagnetic waves. In other words, the expanded beads of the present invention contain a luminescent rare earth element together with the thermoplastic polymer described above. The expanded beads of the present invention can be identified by the luminescence reaction exhibited by irradiation with electromagnetic waves.
[0040] The luminescent reaction is derived from one or more luminescent rare earth elements selected from the group consisting of, for example, praseodymium (Pr), cerium (Ce), neodymium (Nd), samarium (Sm), europium (Eu), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), and thulium (Tm). In other words, the expanded particles of the present invention preferably contain, as a luminescent rare earth element, one or more elements selected from the group consisting of praseodymium (Pr), cerium (Ce), neodymium (Nd), samarium (Sm), europium (Eu), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), and thulium (Tm).More preferably, the expanded particles of the present invention preferably contain, as a luminescent rare earth element, one or more elements selected from the group consisting of praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), and thulium (Tm). In the present invention, the luminescent rare earth element may be a single element or may be used as a compound containing the luminescent rare earth element, so long as it exhibits a luminescent reaction at least when irradiated with electromagnetic waves.
[0041] It is useful to directly or indirectly know the emission spectrum of the luminescence reaction in the expanded beads of the present invention. Based on such knowledge, the expanded beads of the present invention can be distinguished as follows. That is, the expanded beads of the present invention are expanded beads containing a thermoplastic polymer and a luminescent rare earth element component that emits light when irradiated with electromagnetic waves and exhibits a specific emission spectrum. The expanded beads of the present invention can be identified as those containing the luminescent rare earth element by comparing the emission spectrum detected by irradiating the expanded beads with the electromagnetic waves with a preset reference emission spectrum that shows a luminescent reaction derived from the luminescent rare earth element. Details of this identification method will be described later. Here, "directly recognizing information on what kind of emission spectrum the luminescence reaction shows" means to directly obtain the pattern of the actual light intensity and wavelength of the emission spectrum, whereas "indirectly recognizing the information" means to mechanically identify the foamed beads using a collation system or the like in which a reference emission spectrum pattern is recorded so as to be collatable.
[0042] In this specification, luminescent rare earth elements or compounds containing luminescent rare earth elements may be collectively referred to as luminescent rare earth element components. Luminescent rare earth element components include taggant particles, which will be described later.
[0043] In one aspect of the present invention, the expanded beads of the present invention may contain taggant particles containing a luminescent rare earth element. In the present invention, the taggant particles are luminescent rare earth element components and particulate identifiers that enable identification by a luminescent reaction. From the viewpoint of facilitating a stable luminescent reaction, the taggant particles are preferably a compound containing a luminescent rare earth element. However, the taggant, which is the identifier, is not necessarily limited to particles.
[0044] The shape of the taggant particles is not particularly limited, and may take various shapes such as a sphere, an elliptical sphere (egg-shaped), a cylinder, a prism, a pellet, or a granular shape. As one embodiment of the taggant particles, for example, the taggant particles are fine powders having an average particle diameter of 0.1 μm to 100 μm, preferably 1 μm to 50 μm. In this case, the fine particle taggant particles can be more uniformly dispersed in the thermoplastic polymer constituting the expanded particles, and the detection accuracy of the luminescence reaction can be further improved. The average particle diameter of the taggant particles is a value measured by the following method. First, the taggant particles are observed using a scanning electron microscope and an image is taken. The area (projected area) of the particles is measured by analyzing the image, and the diameter of a virtual perfect circle having the same area as the projected area is taken as the particle diameter of the particle. This measurement is performed for 100 or more particles, and the arithmetic average value is taken as the average particle diameter of the taggant particles.
[0045] Examples of taggant particles, which are particulate composites containing luminescent rare earth elements, include, for example, crystalline ligands obtained by the reaction of luminescent rare earth elements with unsaturated organic ligands, and crystalline ligands obtained by the reaction of luminescent rare earth elements, non-luminescent rare earth elements, and unsaturated organic ligands. More specifically, the crystalline ligands are composites obtained by coordinating one or more luminescent rare earth elements to an unsaturated organic ligand. Examples of the unsaturated organic ligands include phthalates, isophthalates, terephthalates, trimesates, trimellitates, pyromellitates, and mellitates.
[0046] The taggant particles, which are composites, are advantageous in that they can realize a wide variety of emission spectra by designing the type and combination of luminescent rare earth elements used. For example, a specific emission spectrum exhibited by a molded product made of a polymer composition of a predetermined composition containing a certain taggant particle when irradiated with electromagnetic waves of a specific wavelength may be pre-linked to the properties of the material constituting the expanded beads, the physical properties of the expanded beads such as apparent density, production conditions such as production lot number and production date, and source information such as manufacturer. The molded product is preferably an expanded bead or an expanded bead molding. This allows the taggant particle to more effectively function as a particulate identifier that enables identification by a luminescent reaction. Specifically, the pre-linked source information can be obtained from the expanded beads containing the taggant particle or its molding by the second identification method described later.
[0047] When the crystalline ligand is irradiated with electromagnetic waves, light energy is transferred to the luminescent rare earth element via the organic ligand contained in the composite, and as a result, the luminescent rare earth element becomes excited, and then undergoes a luminescence reaction in which light of a specific wavelength, such as visible light, is emitted, and the luminescent rare earth element returns to the ground state. In order to maximize the energy of the electromagnetic waves transmitted to the luminescent rare earth element via the organic ligand, the organic ligand is preferably selected to have a structure that exhibits optimal absorption in the range of wavelengths of the electromagnetic waves selected for excitation, in other words, the electromagnetic waves are selected from the range of wavelengths that can be optimally absorbed by the organic ligands contained in the composite.
[0048] From the viewpoint of making it easy to detect the luminescence reaction due to electromagnetic wave irradiation and preventing a decrease in the moldability of the expanded beads, the taggant particle content Ctt in the expanded beads of the present invention is preferably 0.0001 mass % or more and 0.5 mass % or less. From the viewpoint of making the luminescent reaction easier to detect, the lower limit of the content Ctt is more preferably 0.0005% by mass or more, and further preferably 0.001% by mass or more. On the other hand, from the viewpoint of further suppressing the increase in costs due to the use of taggant particles containing expensive luminescent rare earth elements, from the viewpoint of providing expanded beads having superior moldability, and from the viewpoint of providing expanded beads having superior uniformity of cell diameter, the upper limit of the content Ctt is more preferably 0.1 mass% or less, even more preferably 0.05 mass% or less, and particularly preferably 0.03 mass% or less.
[0049] For compounds containing luminescent rare earth elements, reference can be made to, for example, JP 2006-249075 A, JP 2022-187940 A, and US 2010 / 0207067 A.
[0050] (Electromagnetic waves) The electromagnetic waves used to cause the luminescent rare earth elements to emit light may be appropriately selected depending on the types and combination of the luminescent rare earth elements contained in the expanded beads. Examples of electromagnetic waves include infrared rays, visible light rays, ultraviolet rays, X-rays, and gamma rays, but in terms of ease of handling and simple use, it is preferable to use light rays as electromagnetic waves, and it is more preferable to use ultraviolet rays in particular. In other words, the taggant particles that show a luminescent reaction due to the light rays are preferable in the present invention. In addition, the light rays to be irradiated may be single-wavelength having a single wavelength, or may be broad-wavelength having multiple wavelengths. In particular, it is particularly preferred that the expanded beads of the present invention do not show a luminescent reaction when irradiated with visible light, but show a luminescent reaction when irradiated with ultraviolet light. In this case, the taggant particles composed of the luminescent rare earth element cannot be seen with the naked eye by visible light, so that the aesthetic appearance of the expanded bead molding is prevented from being impaired.
[0051] (Mold of foam particles) Next, the configuration and form of the expanded beads of the present invention will be described with reference to Figs. 1 to 4. The shape of the expanded beads is not particularly limited, and may be various shapes such as spherical, elliptical, cylindrical, and cylindrical. Figs. 1 to 3 are schematic cross-sectional views showing a cut surface cut through the center of a spherical expanded bead 100, and Fig. 4 is a schematic cross-sectional view along the axial direction of a two-layer cylindrical type expanded bead 100. The configuration and form of the expanded beads of the present invention can be appropriately designed within the scope that does not impair the object and effect of the present invention, and as described below, some preferable configurations and forms can be mentioned.
[0052] The expanded beads 100A shown in Fig. 1 are spherical and single-layered. That is, the expanded beads 100A are entirely composed of an expanded layer 20, with taggant particles 10 dispersed therein. The expanded beads 100A having a single layer have the advantages of being easy to manufacture and easy to reduce in weight. However, the expanded beads of the present invention are not limited to the single layer form. Examples of the expanded beads of the present invention having a multi-layer structure will be described below with reference to Figs. 2 to 4.
[0053] The expanded beads 100 (100B, 100C, 100D) shown in Fig. 2 to Fig. 4 have a multilayer structure including a foamed layer 20 made of a thermoplastic polymer and a polymer layer 30 made of a polymer. The expanded beads having a multilayer structure are a more preferred embodiment because they exhibit various advantageous advantages, as described below. In such a multi-layer structure, the ratio [Ctr / Ctt] of the content Ctr of the taggant particles 10 in the polymer layer 30 to the content Ctt of the taggant particles 10 in the expanded beads 100 is preferably 2 or more, more preferably 5 or more, even more preferably 10 or more, and particularly preferably 20 or more. By having a relatively large amount of taggant particles 10 in the polymer layer 30 in this way, the concentration of the taggant particles 10 can be locally increased in the polymer layer 30 while maintaining the content Ctt of the taggant particles 10 in the entire expanded beads 100 low. As a result, in the polymer layer 30 of the multi-layered expanded beads 100, the collision probability between the irradiated electromagnetic wave and the taggant particles 10 increases, and a light emission reaction can occur efficiently. In addition, by having a relatively large amount of taggant particles 10 in the polymer layer 30, it is easy to suppress the taggant particles 10 from adversely affecting the foaming state of the foamed layer 20, and more uniform bubbles are easily formed in the foamed layer 20. The upper limit of the ratio [Ctr / Ctt] is preferably 100 or less, and more preferably 50 or less, from the viewpoint of suppressing inhibition of the fusibility of the expanded beads. With respect to the expanded beads of the present invention, the content of taggant particles refers to the ratio (mass %) of the mass of the taggant particles contained in the expanded beads to the mass of the expanded beads.
[0054] In addition, an embodiment in which the taggant particle content Ctt in the multilayered expanded beads 100 is 0.0001 mass% or more and 0.5 mass% or less, and the ratio [Ctr / Ctt] of the taggant particle 10 content Ctr in the polymer layer 30 to the taggant particle 10 content Ctt in the expanded beads 100 is 2 or more, is excellent in that it reduces the amount of taggant particles 10 used and increases the efficiency of the luminescence reaction without impairing the foamed state of the expanded beads 100.
[0055] As described above, in the multilayer structure, it is particularly preferable that the following embodiment is further added to expanded beads having a ratio [Ctr / Ctt] of the content Ctr of taggant particles 10 in the polymer layer 30 to the content Ctt of taggant particles 10 in the expanded beads 100 of 2 or more. That is, from the viewpoint of making it possible to sufficiently increase the content of taggant particles 10 in the polymer layer 30 and efficiently causing a luminescent reaction, in addition to the above embodiment, the mass proportion of the polymer layer 30 in the expanded beads 100 is preferably 0.5% by mass or more and 15% by mass or less, more preferably 1% by mass or more and 10% by mass or less, and even more preferably 2% by mass or more and 8% by mass or less.
[0056] The foamed layer 20 in the expanded beads 100B, 100C, and 100D may or may not contain taggant particles 10. However, from the viewpoint of maintaining a good foamed state of the foamed layer 20 and reducing the amount of taggant particles 10 used to improve economic efficiency, the content of taggant particles 10 in the foamed layer 20 is preferably 0.1% by mass or less, more preferably 0.01% by mass or less, even more preferably 0.001% by mass or less, particularly preferably 0.0001% by mass or less, and preferably 0, i.e., the foamed layer 20 does not contain taggant particles 10.
[0057] Here, the multilayered expanded beads 100 are, for example, as shown in FIG. 2, spherical and have a foamed layer 20 as a core layer and a polymer layer 30 as a coating layer that coats the foamed layer 20, and an example of the expanded beads 100B is an expanded bead 100B in which the polymer layer 30 is located on the surface of the expanded bead. As another embodiment, as shown in FIG. 3, there is an expanded bead 100C having a spherical shape and including a foamed layer 20 as a core layer, an outermost layer 40 provided on the surface of the expanded bead, and a polymer layer 30 as an intermediate layer located between the foamed layer 20 and the outermost layer 40. The outermost layer 40 can be made of any material, for example, a foamed thermoplastic polymer or a non-foamed thermoplastic polymer. In order to sufficiently generate a light-emitting reaction in the intermediate polymer layer 30, the outermost layer 40 is preferably a layer through which electromagnetic waves can easily pass, and more preferably a layer through which ultraviolet rays or visible light, which are preferably selected as electromagnetic waves, can easily pass. For example, the outermost layer 40 may be made of a polymer or the like that is transparent or white in color. Another embodiment is, as shown in Fig. 4, an expanded bead 100D having a cylindrical shape and including a foamed layer 20 as a core layer and a polymer layer 30 as a coating layer that coats the lateral peripheral surface of the foamed layer 20, with the polymer layer 30 located on the surface of the expanded bead. Fig. 4 shows an embodiment in which the polymer layer 30 is provided on the entire peripheral surface in the length direction of the expanded bead 100D, and the foamed layer 20 is exposed at the end surface 21 in the length direction. However, as a modified example, the expanded bead 100D may have the polymer layer 30 covering the entire foamed layer 20, including the end surface 21. Although not shown in the figures, the expanded beads of the present invention are not limited to an embodiment in which a polymer layer is provided on the surface side of a foam layer, but also include an embodiment in which a polymer layer is provided closer to the center of the expanded beads than the foam layer.
[0058] 2 and 3 show an embodiment in which the polymer layer 30, which is a coating layer, covers the entire foamed layer 20, but the present invention also includes an embodiment in which the polymer layer 30 partially covers the foamed layer 20, as in the foamed bead 100D shown in FIG. 4, within the scope of the present invention, so long as the object and effect of the present invention are not hindered. From the viewpoint of increasing the detection accuracy of the luminescent reaction, the expanded beads 100 having a multilayer structure having a polymer layer 30 covering the foamed layer 20 are preferably composed of the foamed layer 20 and the polymer layer 30 covering 30% or more of the surface area of the foamed layer 20. From the same viewpoint, it is more preferable that the polymer layer 30 covers 50% or more of the surface area of the foamed layer 20, and further preferably covers 70% or more.
[0059] In the above-mentioned multi-layered expanded beads 100, the expanded beads 100B and 100D in which the polymer layer 30 is located on the surface of the expanded beads in particular can efficiently absorb the energy of the irradiated electromagnetic waves into the taggant particles 10 contained in the polymer layer 30. Therefore, the expanded beads 100B and 100D cause a good luminescence reaction, and as a result, the emission spectrum in the luminescence reaction can be detected with high accuracy.
[0060] However, even in the case where the polymer layer 30 does not appear on the surface of the expanded beads 100 as in the expanded beads 100C, if the polymer layer 30 is provided near the surface of the multi-layered expanded beads 100, the taggant particles 10 contained in the polymer layer 30 can efficiently absorb the energy of the irradiated electromagnetic waves, as in the case of the expanded beads 100B and 100D. In other words, the polymer layer 30 is preferably provided on or near the surface of the multi-layered expanded beads 100. The polymer layer 30 being provided near the surface of the multi-layered expanded beads 100 means that at least a part of the polymer layer 30 is located in a region d1 from the surface of the multi-layered expanded beads 100 to a depth of 1000 μm toward the center, as shown in FIG. 3, for example.
[0061] In the multi-layered expanded beads 100 including the above-mentioned expanded layer 20 and polymer layer 30, from the viewpoint of efficiently causing the luminescence reaction of the expanded beads 100 and improving the detection accuracy, the content Ctr of the taggant particles 10 in the polymer layer 30 is preferably 0.001% by mass or more, more preferably 0.005% by mass or more, and even more preferably 0.01% by mass or more. On the other hand, from the viewpoint of obtaining expanded beads having excellent moldability without inhibiting the fusibility of the expanded beads, the content Ctr of the taggant particles 10 in the polymer layer 30 is preferably 5% by mass or less, more preferably 1% by mass or less, even more preferably 0.5% by mass or less, and particularly preferably 0.1% by mass or less.
[0062] Furthermore, it is further preferable that the expanded beads 100 have (i) a ratio [Ctr / Ctt] of the content Ctr of taggant particles 10 in the polymer layer 30 to the content Ctt of taggant particles 10 in the expanded beads 100 having a foam layer 20 and a polymer layer 30 of 2 or more, and (ii) the content Ctr of taggant particles 10 in the polymer layer 30 is 0.001 mass% or more and 5 mass% or less. According to this embodiment, the concentration of the taggant particles 10 in the polymer layer 30 can be increased while keeping the amount of taggant particles 10 used in the entire expanded beads 100 small. As a result, the expanded state of the expanded beads 100 can be maintained better, and the luminescent reaction of the expanded beads 100 can be efficiently caused, thereby improving detection accuracy. Furthermore, the expanded beads 100 of this embodiment have excellent moldability, since the fusion between the expanded beads is less likely to be hindered during the production of an expanded bead molding.
[0063] Furthermore, in addition to the above (i) and (ii), the expanded beads 100 preferably have (iii) a content Ctt of taggant particles 10 in the expanded beads 10 of 0.0001% by mass or more and 0.5% by mass or less. The expanded beads 100 of this embodiment are excellent in terms of moldability, occurrence of a significant luminescence reaction, and suppression of the amount of taggant particles 10 used. Furthermore, the expanded beads 100 of this embodiment are excellent in moldability, since the fusion between the expanded beads is less likely to be inhibited during the production of an expanded bead molding.
[0064] Furthermore, in addition to the above (i), (ii), and (iii), it is preferable that the expanded beads 100 have (iv) a polymer layer 30 located on the surface of the expanded beads 100. According to this embodiment, the concentration of the taggant particles 10 in the polymer layer 30 located on the surface can be increased while keeping the amount of taggant particles 10 used in the entire expanded beads 100 small. As a result, the expanded state of the expanded beads 100 can be maintained in a good state, and the luminescence reaction of the expanded beads 100 can be caused more efficiently, thereby significantly improving detection accuracy. Moreover, the expanded beads 100 of this embodiment have excellent moldability, since the fusion between the expanded beads is less likely to be hindered during the production of an expanded bead molding.
[0065] The thermoplastic polymer constituting the foamed layer 20 in the multi-layered foamed beads 100 can be appropriately selected from the various thermoplastic polymers used to form the thermoplastic polymer foamed beads described above. The polymer constituting the polymer layer 30 is not limited to a thermoplastic polymer. The polymer constituting the polymer layer 30 may be the same as the thermoplastic polymer constituting the foamed layer 20, or a different polymer may be used. The method for obtaining the multi-layered expanded beads having the polymer layer 30 covering the foamed layer 20 described above is not particularly limited, but examples of the method include a method in which, in the production of thermoplastic polymer particles described later, polymer particles having a coating layer laminated on the surface of a core layer are obtained by co-extrusion using an extruder, and at least the core layer of the polymer particles is expanded, and a method in which a single-layer expanded particle is obtained and a powdery polymer is coated on the surface of the single-layer expanded particle.
[0066] The polymer layer 30 located on the surface of the foamed particles 100 preferably has the following aspects from the viewpoint of improving the fusion property between the foamed particles during the production of the foamed particle molded body. That is, it is preferable that the polymer constituting the polymer layer 30 is a thermoplastic polymer. Further, it is preferable that the melting point or softening point of the polymer constituting the polymer layer 30 is lower than the melting point of the thermoplastic polymer constituting the foamed layer 20. By realizing such a temperature relationship, even when the content of the tagant particles 10 contained in the polymer layer 30 is relatively large, the fusion property between the foamed particles is hardly inhibited. From such a viewpoint, it is preferable that the melting point Tms of the thermoplastic polymer constituting the polymer layer 30 is lower than the melting point Tmc of the thermoplastic polymer constituting the foamed layer 20, for example. That is, it is preferable that Tms < Tmc. Even when the content of the tagant particles 10 contained in the polymer layer 30 is relatively large, from the viewpoint of sufficiently enhancing the fusion property between the foamed particles, it is preferable that Tmc - Tms ≧ 3, more preferably Tmc - Tms ≧ 5, and even more preferably Tmc - Tms ≧ 8. From the viewpoint of suppressing the peeling between the foamed layer 20 and the polymer layer 30, it is preferable that Tmc - Tms ≦ 35, more preferably Tmc - Tms ≦ 20, and even more preferably Tmc - Tms ≦ 15.
[0067] The melting point Tmc of the thermoplastic polymer constituting the foamed layer 20 depends on the type of the thermoplastic polymer constituting the foamed layer 20, but is generally 100°C or higher and 250°C or lower, preferably 110°C or higher and 200°C or lower, more preferably 120°C or higher and 180°C or lower, and even more preferably 140°C or higher and 160°C or lower. Further, the melting point Tms of the thermoplastic polymer constituting the polymer layer 30 is generally 80°C or higher and 180°C or lower, preferably 100°C or higher and 150°C or lower, and more preferably 105°C or higher and 140°C or lower. Although there are no particular limitations on the combination of the thermoplastic polymer constituting the foamed layer 20 and the thermoplastic polymer constituting the polymer layer 30, it is preferable that the thermoplastic polymer constituting the foamed layer 20 is a polyolefin-based resin, and the thermoplastic polymer constituting the polymer layer 30 is a polyolefin-based resin. In this case, it is preferable that the difference [Tmc-Tms] between the melting point Tmc of the polyolefin-based resin constituting the foamed layer and the melting point Tms of the polyolefin-based resin constituting the polymer layer is 3°C or more and 35°C or less.
[0068] The melting point of a thermoplastic polymer is determined based on JIS K7121:1987. Specifically, the conditioning is performed by "(2) Measuring the melting temperature after a certain heat treatment", conditioning is performed at a heating rate and cooling rate of 10°C / min, and the condition-conditioned test piece is heated from 30°C to 200°C at a heating rate of 10°C / min to obtain a DSC curve, and the apex temperature of the melting peak in the DSC curve is taken as the melting point. Note that when multiple melting peaks appear in the DSC curve, the apex temperature of the melting peak with the largest area is taken as the melting point.
[0069] The polymer layer 30 may be in a foamed state or a non-foamed state. From the viewpoint of further increasing the detection accuracy of the taggant particles 10 contained in the polymer layer 30, it is preferable that the polymer layer 30 is substantially in a non-foamed state. Being substantially in a non-foamed state includes a state in which the polymer layer 30 is not foamed and does not contain bubbles, and a state in which bubbles have disappeared after foaming, and means that there is almost no bubble structure.
[0070] The presence of a rare earth element in the expanded beads can be confirmed by known elemental analysis methods such as inductively coupled plasma mass spectrometry (ICP-MS) and X-ray fluorescence elemental analysis (XRF). From the viewpoint of low cost and ensuring a luminescent reaction, the content of the luminescent rare earth element in the expanded beads is preferably 0.4 ppm or more and 2000 ppm or less, more preferably 2 ppm or more and 400 ppm or less, even more preferably 4 ppm or more and 200 ppm or less, and particularly preferably 4 ppm or more and 120 ppm or less. The content of the luminescent rare earth element in the expanded beads is measured by performing inductively coupled plasma mass spectrometry (ICP-MS) on the expanded beads as a sample. From the same viewpoint, the content of the luminescent rare earth element in the polymer layer of the expanded beads having a foam layer and a polymer layer is preferably 4 ppm or more and 12500 ppm or less, more preferably 12 ppm or more and 4000 ppm or less, further preferably 40 ppm or more and 1250 ppm or less, and particularly preferably 40 ppm or more and 400 ppm or less. The content of the luminescent rare earth element in the polymer layer can be measured in the same manner as the measurement of the content of the luminescent rare earth element in the expanded beads, except that the polymer layer is used as the measurement sample.
[0071] The content of taggant particles in expanded beads can be calculated from the content of luminescent rare earth elements in the expanded beads by, for example, determining the composition of the taggant particles contained in the expanded beads in advance. Determining the composition of the taggant particles in advance means, for example, in the case where the taggant particles are crystalline ligands obtained by the reaction of a luminescent rare earth element with an unsaturated organic ligand, determining the composition, i.e., the types and component ratios of the luminescent rare earth element and the unsaturated organic ligand, in advance by a method such as chemical analysis.
[0072] (carbon particles) The expanded beads of the present invention may contain carbon particles. For example, in order to provide a black expanded bead molding, the expanded beads may contain carbon particles that are a black pigment. The carbon particles are added for the purpose of imparting a black color to the expanded beads and / or imparting functionality such as electrical conductivity. When carbon particles are contained, the carbon particle content Cct in the expanded beads is preferably 0.01% by mass or more and 15% by mass or less, more preferably 0.1% by mass or more and 12% by mass or less, even more preferably 1% by mass or more and 10% by mass or less, and even more preferably 1.5% by mass or more and 5% by mass or less. In particular, when the carbon particles are black pigments, the above numerical ranges have the following effects. That is, by making the carbon particle content Cct in the expanded beads 0.01% by mass or more, it is possible to obtain an expanded bead molding having a high degree of blackness, for example an L* value of 30 or less. Expanded bead moldings with a high degree of blackness are preferable from the viewpoint of aesthetics, since they give the molding a high-class feel. On the other hand, in order to prevent a decrease in the detection accuracy of the luminescence reaction of the expanded beads due to the carbon particles, it is preferable that the carbon particle content Cct in the expanded beads is 15% by mass or less. In other words, the expanded beads of the present invention, in which the carbon particle content Cct is adjusted to the above-mentioned range, are black in color, but can be identified by the luminescence reaction.
[0073] From the viewpoint of obtaining a molded article with a high degree of blackness and enabling detection of a luminescence reaction with higher accuracy, expanded beads having a foamed layer made of a thermoplastic polymer and a polymer layer covering the foamed layer, a ratio [Ctr / Ctt] of the taggant particle content Ctr in the polymer layer to the taggant particle content Ctt in the expanded beads being 2 or more, and a carbon particle content Cct being 0.01% by mass or more and 15% by mass or less are preferred. Among these, it is more preferred that the polymer layer is provided on or near the surface of the expanded beads, and that the carbon particle content in the expanded beads is within the above range. This provides expanded beads that have a black appearance and are easily identifiable by a luminescence reaction.
[0074] According to the study of the present invention, it was considered that, for example, when carbon particles are contained in the expanded beads in order to obtain an expanded bead molding with a high degree of blackness, at least a part of the electromagnetic waves irradiated to identify the expanded beads or the light generated by the electromagnetic wave irradiation tends to be absorbed by the carbon particles, resulting in a decrease in the accuracy of light detection. However, according to the above-mentioned embodiment of the present invention in which taggant particles are contained in the polymer layer, even when carbon particles are blended, it is possible to provide expanded beads that have a black appearance and are easily identifiable by the luminescence reaction by suppressing the inhibition of the luminescence reaction of the expanded beads.
[0075] When the expanded beads of the present invention are multi-layer expanded beads having a foam layer and a polymer layer, it is preferable that the carbon particles are contained in both the foam layer and the polymer layer, and that the taggant particles are contained in the polymer layer. The content of the carbon particles in the foam layer and the polymer layer is preferably within the same range as the content of the carbon particles in the expanded beads. This provides expanded beads that have good identifiability by luminescence reaction and a beautiful black appearance with suppressed color unevenness.
[0076] The carbon particles, which are black pigments, refer to particles that contain carbon, and examples thereof include one or more materials selected from carbon black, conductive carbon, carbon nanotubes, graphene, graphite, activated carbon, etc. Among these, carbon black is preferred from the viewpoint of excellent balance between dispersibility in polymers such as resins and cost. Examples of carbon black include channel black, roller black, furnace black, thermal black, acetylene black, and ketjen black.
[0077] The expanded beads of the present invention may contain any additives as appropriate within the scope of not impairing the objects and effects of the present invention. For example, the optional additives include a flame retardant, a flame retardant assistant, a cell regulator, a lubricant, a crystal nucleating agent, a conductive material, an antistatic agent, etc.
[0078] (Average bubble diameter) The expanded beads of the present invention are produced by expanding polymer particles as a raw material, and have a cell structure containing a large number of cells. From the viewpoint of improving the moldability of the expanded beads, the average cell diameter in the expanded beads of the present invention is preferably 20 μm or more, more preferably 30 μm or more, even more preferably 50 μm or more, and particularly preferably 80 μm or more. On the other hand, from the viewpoint of improving the surface smoothness of the molded body, the average bubble diameter in the expanded beads of the present invention is preferably 250 μm or less, more preferably 200 μm or less, even more preferably 180 μm or less, and preferably 150 μm or less.
[0079] The average cell diameter of the expanded beads is determined as follows. First, the expanded bead is cut into two equal parts. Next, a photograph of the cross section is taken so that the exposed cut surface is entirely within the field of view. On the photograph, four lines are drawn from the outermost surface of the expanded bead through the center to the outermost surface on the opposite side, with the angle between adjacent lines being equal. In other words, the lines are drawn so that the angle between adjacent lines is 45°. The total length L of the four lines thus obtained is divided by the number N of all the bubbles in contact with the lines, and the value (L / N) is taken as the average bubble diameter of one expanded bead. This operation is performed for 10 or more expanded beads, and the arithmetic average value is taken as the average bubble diameter of the expanded beads.
[0080] When the expanded beads of the present invention are used to produce an expanded bead molding by in-mold molding, from the viewpoint of easily exhibiting excellent moldability and easily obtaining a molded body with little color unevenness, it is preferable that the average cell diameter of the thermoplastic polymer expanded beads is 20 μm or more and 250 μm or less, and that the coefficient of variation of the cell diameter is 30% or less, more preferably that the average cell diameter of the thermoplastic polymer expanded beads is 30 μm or more and 200 μm or less, and that the coefficient of variation of the cell diameter is 25% or less, even more preferably that the average cell diameter of the thermoplastic polymer expanded beads is 50 μm or more and 180 μm or less, and that the coefficient of variation of the cell diameter is 20% or less, and even more preferably that the average cell diameter of the thermoplastic polymer expanded beads is 80 μm or more and 150 μm or less, and that the coefficient of variation of the cell diameter is 15% or less. Such a preferred configuration is easily realized by an expanded bead having, for example, a foamed layer made of a thermoplastic polymer and a polymer layer, in which the taggant particle content Ctt in the expanded bead is 0.0001% by mass or more and 0.5% by mass or less, and the ratio [Ctr / Ctt] of the taggant particle content Ctr in the polymer layer to the taggant particle content Ctt in the expanded bead is 2 or more. In the embodiment of the expanded bead having a high degree of blackness described above, it is more preferable that the polymer layer is a coating layer that covers the foamed layer. This is because the luminescent reaction can be detected well by providing the polymer layer, in which the taggant particles are concentrated, on the surface side of the expanded bead.
[0081] The expanded beads of the present invention, in which the carbon particle content Cct in the expanded beads is 0.01% by mass or more and 15% by mass or less, the average bubble diameter of the thermoplastic polymer expanded beads is 20 μm or more and 250 μm or less, and the coefficient of variation of the bubble diameter is 30% or less, have excellent moldability and are easy to obtain an expanded bead molding having a black appearance and small color unevenness. The reason why the color unevenness is easily suppressed due to the small coefficient of variation of the bubble diameter is thought to be because the thickness of the bubble film is easily made more uniform. From this viewpoint, it is more preferable that the average bubble diameter of the thermoplastic polymer expanded beads is 30 μm or more and 200 μm or less, and the coefficient of variation of the bubble diameter is 25% or less, more preferably that the average bubble diameter of the thermoplastic polymer expanded beads is 50 μm or more and 180 μm or less, and the coefficient of variation of the bubble diameter is 20% or less, and particularly preferably that the average bubble diameter of the thermoplastic polymer expanded beads is 80 μm or more and 150 μm or less, and the coefficient of variation of the bubble diameter is 15% or less. The expanded beads of the present invention having the above-mentioned black appearance can be easily realized, for example, by expanded beads having a carbon particle content Cct of 0.01% by mass to 15% by mass, a foamed layer made of a thermoplastic polymer, a polymer layer, a taggant particle content Ctt of 0.0001% by mass to 0.5% by mass, and a ratio [Ctr / Ctt] of the taggant particle content Ctr in the polymer layer to the taggant particle content Ctt in the expanded beads of 2 or more. In the embodiment of the expanded beads having a high blackness described above, it is more preferable that the polymer layer is a coating layer that covers the foamed layer. This is because the luminescence reaction can be detected well by providing the polymer layer on the surface side of the expanded beads where the taggant particles are concentrated.
[0082] In order to improve the detection accuracy of the luminescence reaction of the expanded beads, when a relatively large amount of taggant particles are blended in the expanded beads, the taggant particles may also act as nuclei for bubble formation, and the expanded state of the expanded beads may be impaired, for example, causing an increase in the coefficient of variation of the bubble diameter. In particular, in the case of black expanded beads containing carbon particles, it was necessary to blend a larger amount of taggant particles, and there was a risk that the expanded state of the expanded beads may be easily impaired. In contrast, according to the above-mentioned embodiment of the present invention having a polymer layer containing taggant particles, the taggant particles can be unevenly distributed in the polymer layer in the expanded beads, so that there is no risk of the expanded state of the expanded beads being impaired, and expanded beads with good identifiability by luminescence reaction are provided.
[0083] The coefficient of variation can be calculated by dividing the standard deviation of the cell diameters of the expanded beads by the average cell diameter of the expanded beads and multiplying the result by 100. The value given by the square root of the unbiased variance is defined as the standard deviation.
[0084] (Bulk density of expanded particles) The bulk density of the expanded beads of the present invention is not particularly limited, but from the viewpoint of weight reduction, it is preferably 150 kg / m 3 It is preferable that the density is less than 100 kg / m 3 More preferably, it is 50 kg / m or less. 3 From the viewpoint of the rigidity of the foamed bead molding produced by using the foamed beads, the bulk density of the foamed beads is preferably 10 kg / m or less. 3 It is preferable that the saturation temperature is 15 kg / m or more. 3 More preferably, it is 20 kg / m or more. 3 More preferably, it is equal to or greater than this.
[0085] The bulk density of expanded beads is measured by the following method. First, the expanded beads to be measured are conditioned by leaving them to stand for at least 24 hours in an environment of 23°C temperature, 50% relative humidity, and 1 atm. After conditioning, the expanded beads with mass W (g) are filled into a measuring cylinder so that they naturally accumulate, and the bottom of the measuring cylinder is lightly tapped several times against a horizontal surface to stabilize the filling height of the expanded beads in the measuring cylinder. The bulk volume V (L) of the expanded beads indicated by the graduations on the measuring cylinder is read, and the mass W of the expanded beads is divided by the bulk volume V of the expanded beads (W / V), and the unit conversion is performed to obtain the bulk density of the expanded beads (kg / m 3 ) can be obtained.
[0086] (High temperature peak) The expanded beads of the present invention preferably have a crystal structure exhibiting a high-temperature peak as described below. Expanded beads exhibiting a high-temperature peak are preferred from the viewpoint of a wider range of molding conditions under which a good expanded bead molding can be obtained. The crystal structure exhibiting a high-temperature peak can be formed when the thermoplastic polymer constituting the expanded beads is a crystalline polymer.
[0087] Here, the high-temperature peak refers to a melting peak whose apex appears at a higher temperature than the melting peak inherent to the thermoplastic polymer in the first DSC curve (see FIG. 7) measured by heat flux differential scanning calorimetry based on JIS K7122-1987, when a test piece of 1 to 3 mg of expanded beads is heated and melted from 30°C to a temperature 30°C higher than the melting end temperature at a heating rate of 10°C / min. In this specification, the melting peak inherent to the thermoplastic polymer may be referred to as inherent peak a, and the melting peak whose apex appears at a higher temperature than inherent peak a may be referred to as high-temperature peak b. FIG. 7 is an example of a DSC curve measured based on heat flux differential scanning calorimetry of expanded beads. Although one high-temperature peak b is shown in FIG. 7, there may be two or more high-temperature peaks b.
[0088] The characteristic peak a is a peak generated by melting of the inherent crystals of the thermoplastic polymer that is the base material constituting the expanded beads, and is considered to be a peak that appears due to melting of the crystals that the base material constituting the expanded beads normally has. On the other hand, the high-temperature peak b is presumed to appear when secondary crystals different from the crystals that are normally present in the base material constituting the expanded beads are present. The method for obtaining the expanded beads having the above-mentioned high-temperature peak b will be described later.
[0089] From the viewpoint of obtaining an expanded bead molding having an excellent balance between cushioning properties and rigidity, the heat of fusion of the high-temperature peak b is preferably 5 J / g or more, more preferably 7 J / g or more, and even more preferably 10 J / g or more. From the viewpoint of reducing the pressure of steam capable of molding during in-mold molding of the expanded beads, the heat of fusion of the high-temperature peak b is preferably 30 J / g or less, more preferably 28 J / g or less, and even more preferably 25 J / g or less. When two or more high-temperature peaks b appear, the heat of fusion of the high-temperature peaks b means the total heat of all the high-temperature peaks b. For the method of calculating the heat of fusion of the high-temperature peak b, see the description in the Examples section below.
[0090] From the viewpoint of improving the filling property into the molding die, the average particle size of the expanded beads is preferably 0.3 mm or more and 8 mm or less, more preferably 0.5 mm or more and 5 mm or less, and further preferably 0.8 mm or more and 4.5 mm or less. The average particle diameter of the expanded beads is a value obtained by the following method. First, based on the volume-based particle size distribution of the expanded beads, the shape of the particles is assumed to be spherical, and the particle size distribution is converted to a number-based particle size distribution to obtain the number-based particle size distribution. Then, the particle diameters based on this number-based particle size distribution are arithmetically averaged to obtain the number-based arithmetic average particle diameter. The particle diameter means the diameter of a virtual sphere having the same volume as the particles. The particle size distribution of the expanded beads on a volume basis can be measured using a particle size distribution measuring device (for example, "Militrack JPA" manufactured by Nikkiso Co., Ltd.). The number of expanded beads used for the measurement may be, for example, 2000 or more.
[0091] From the same viewpoint, the average mass of the expanded beads is preferably 0.2 mg or more and 5 mg or less, more preferably 0.5 mg or more and 4 mg or less, and further preferably 0.8 mg or more and 3 mg or less. The average mass of the expanded beads can be obtained by randomly selecting 100 or more expanded beads, measuring the mass [mg] of the expanded beads, and dividing the mass by the number of expanded beads used in the measurement.
[0092] (Method of manufacturing thermoplastic polymer foam particles) The expanded beads of the present invention can be manufactured by following a general manufacturing method of expanded beads, except that a luminescent rare earth element is blended. A general manufacturing method of expanded beads includes, for example, a method of preparing thermoplastic polymer particles, impregnating the thermoplastic polymer particles with a blowing agent, and then expanding the particles. An example of the manufacturing method of the expanded beads of the present invention will be described below.
[0093] First, a thermoplastic polymer and a luminescent rare earth element component are put into an extruder, melt-kneaded to prepare a melt-kneaded product, and the melt-kneaded product is extruded from the extruder to prepare thermoplastic polymer particles. In general, the melt-kneaded product extruded from the extruder is cut by a pelletizer or the like, and the mass and shape are adjusted to form small pellet-shaped thermoplastic polymer particles. The melt-kneaded product may contain any additive as appropriate. In addition, a luminescent rare earth element component may be incorporated in the thermoplastic polymer before preparing the thermoplastic polymer particles.
[0094] When producing multi-layered expanded beads, it is advisable to prepare a melt-kneaded mixture for forming a core layer constituting the core layer and a melt-kneaded mixture for forming a coating layer constituting the coating layer covering the core layer, and to produce multi-layered thermoplastic polymer particles using a production device equipped with an extruder for forming a core layer, a die for forming a multi-layered strand attached to the downstream side of the extruder for forming a core layer, and an extruder for forming a coating layer. The production device is connected to the downstream side of the extruder for forming a polymer layer and a die for forming a multi-layered strand, and is capable of laminating the melt-kneaded mixture for forming each layer in the die and of co-extrusion. In the present invention, the multi-layered thermoplastic polymer particles produced as described above include an embodiment in which the core layer is a foamed layer and the coating layer is a polymer layer that coats the foamed layer, and an embodiment in which the core layer is a polymer layer and the coating layer is a foamed layer that coats the polymer layer.
[0095] Next, the thermoplastic polymer particles obtained as described above, an aqueous medium such as water, an inorganic dispersant, and other optional additives are supplied to a pressure vessel and dispersed in a dispersing step, and the thermoplastic polymer particles are impregnated with a foaming agent in an impregnation step. Examples of the inorganic dispersant include inorganic substances such as aluminum oxide, tricalcium phosphate, magnesium pyrophosphate, zinc oxide, kaolin, mica, talc, smectite, etc. In addition to the dispersant, a dispersing aid such as an anionic surfactant such as sodium dodecylbenzenesulfonate or sodium alkanesulfonate may be added. The foaming agent is appropriately selected from foaming agents that can be used in the production of general expanded beads. Specific examples of the foaming agent include inorganic physical foaming agents such as carbon dioxide, air, nitrogen, helium, argon, and water; and organic physical foaming agents such as propane, butane, hexane, cyclopentane, ethyl chloride, 1,3,3,3-tetrafluoropropene, and 1-chloro-3,3,3-trifluoropropene. Among these foaming agents, foaming agents mainly composed of inorganic physical foaming agents such as carbon dioxide, nitrogen, and air are preferably used, and carbon dioxide is more preferably used. These physical foaming agents may be used alone or in combination of two or more.
[0096] When producing expanded beads showing a high-temperature peak b, it is advisable to adjust the temperature rise rate in the pressure vessel or to hold the temperature in the pressure vessel at a predetermined temperature for a predetermined time in the dispersion step and / or impregnation step described above. More specifically, for example, in the dispersion step and / or impregnation step described above, the temperature in the pressure vessel is held at a temperature between [a temperature 20°C lower than the melting point of the substrate] and [the end temperature of melting of the substrate] for about 10 to 60 minutes. Thereafter, the temperature in the pressure vessel is adjusted to a temperature between [a temperature 15°C lower than the melting point of the substrate] and [the end temperature of melting of the substrate]. Then, if necessary, the temperature is held for another 10 to 60 minutes. The crystal state of the thermoplastic polymer particles is adjusted by such temperature adjustment. The substrate refers to the thermoplastic polymer constituting the thermoplastic polymer particles.
[0097] Next, the thermoplastic polymer particles and the aqueous medium are released into a pressure environment lower than the pressure inside the pressure vessel and expanded, thereby obtaining expanded beads having a high-temperature peak b. When the high-temperature peak b in the expanded beads is not required, the temperature adjustment inside the pressure vessel described above may be omitted as appropriate. The foaming step is not limited to the above method. For example, after the impregnation step, the polymer particles impregnated with the foaming agent can be taken out of the pressure vessel and heated to foam the polymer particles, thereby obtaining foamed particles.
[0098] In order to reduce the bulk density of the first-stage expanded beads obtained by the above-mentioned expansion step, a second-stage expansion step may be further carried out. The second-stage expansion step is a step in which the first-stage expanded beads produced as described above are supplied to a pressure vessel, the first-stage expanded beads are pressurized to increase the pressure (internal pressure) in the cells of the expanded beads, and then heated to expand again. By carrying out the second-stage expansion step, expanded beads having a desired bulk density can be easily produced.
[0099] The manufacturing method of the expanded beads of the present invention is not limited to the above-described manufacturing method. For example, a melt kneaded material not containing a luminescent rare earth element component is prepared to produce thermoplastic polymer particles, which are then expanded to obtain pre-expanded beads. The luminescent rare earth element component is then applied to the pre-expanded beads by any application means to obtain the expanded beads of the present invention. The application means may be a method of sprinkling particulate luminescent rare earth element components on the surface of the pre-expanded particles, in which case the surface of the pre-expanded particles is slightly melted in advance by heating, so that the particulate luminescent rare earth element components can be firmly attached to the surface. As another method for applying the luminescent rare earth element, a liquid in which any luminescent rare earth element component is dispersed is prepared, and the liquid is applied to the pre-foamed particles by spraying or the like, followed by suitable drying.
[0100] [Thermoplastic polymer foamed beads] The expanded bead molding of the present invention is produced by molding the expanded beads of the present invention in a mold. The expanded bead molding of the present invention enjoys the excellent effects of the expanded beads of the present invention. That is, when the expanded bead molding of the present invention is irradiated with electromagnetic waves, the expanded beads constituting the expanded bead molding exhibit a luminous reaction. As a result, the luminous reaction can be detected from the expanded bead molding. Therefore, the expanded bead molding of the present invention can be identified by detecting the luminous reaction.
[0101] Furthermore, the expanded beads themselves that constitute the expanded bead molding can be tracked. Specifically, the expanded bead molding or the expanded beads that constitute it can be identified by checking whether the emission spectrum of the light emission reaction detected from the expanded bead molding shows a similar pattern to a preset reference emission spectrum. The content of taggant particles in the molding (specifically, for example, expanded beads) used to obtain the reference emission spectrum is generally 0.0001% by mass or more and 0.5% by mass or less. Therefore, by knowing the preset reference emission spectrum, according to the present invention, it is possible to trace the expanded beads constituting the expanded bead molding from the expanded bead molding.
[0102] The expanded bead molding of the present invention is suitably used for various applications such as automobile parts, packaging materials, and building materials.
[0103] The expanded bead molding of the present invention is an expanded bead molding obtained by molding expanded beads containing a thermoplastic polymer and a luminescent rare earth element component that emits light when irradiated with electromagnetic waves and shows a specific emission spectrum in a mold. The expanded bead molding of the present invention can be identified as an expanded bead molding made of expanded beads containing the luminescent rare earth element by comparing the emission spectrum detected by irradiating the expanded bead molding with the electromagnetic waves with a preset reference emission spectrum showing a light emission reaction derived from the luminescent rare earth element. Details of this identification method will be described later.
[0104] (Mold density of expanded bead molded body) The density of the expanded bead molding of the present invention is set to 10 kg / m from the viewpoint of excellent balance between light weight and mechanical properties such as rigidity. 3 More than 150kg / m 3 It is preferable that the thickness is less than 15 kg / m 3 More than 100kg / m 3 More preferably, it is 20 kg / m or less. 3 More than 50kg / m 3 It is even more preferable that: The molding density of the expanded bead molding is calculated by dividing the mass of the expanded bead molding by the volume calculated based on the dimensions. If it is difficult to calculate the volume from the external dimensions, the volume of the expanded bead molding can be determined by a submersion method.
[0105] (L* value of expanded bead molding) The present invention can provide a black expanded bead molding by using the expanded beads of the present invention, which exhibit a significant black color. The L* value of the expanded bead molding is, for example, preferably 30 or less, more preferably 28 or less, and even more preferably 25 or less. The L* value of the foamed bead molding is the L* value of the surface of the foamed bead molding in the CIE 1976 L*a*b* color system, and can be measured with a spectrophotometer. The L* value is an index of brightness, and the lower the value, the higher the blackness, meaning that the black is darker.
[0106] Black foamed bead moldings give a sense of luxury to the viewer and therefore tend to be preferred in the field of automobiles, etc. However, black foamed bead moldings generally absorb light and have been considered undesirable from the viewpoint of detecting luminescence reactions. To address this problem, it has been considered to incorporate a sufficiently large amount of taggant particles into the expanded beads, but in this case, the taggant particles act as nuclei for the formation of bubbles, which may reduce the uniformity of the bubbles formed in the expanded beads. Therefore, further studies were made to provide an expanded bead molding that exhibits black color while maintaining a good expanded state of the expanded beads and allows detection of the luminescence reaction. As described above in the description of the expanded beads of the present invention, it was found that it is particularly preferable to use the expanded beads of the present invention having a foam layer and a polymer layer, in which the content Ctt of taggant particles in the expanded beads is 0.0001% by mass or more and 0.5% by mass or less, and the ratio [Ctr / Ctt] of the content Ctr of taggant particles in the polymer layer to the content Ctt of taggant particles in the expanded beads is 2 or more. By significantly increasing the content of taggant particles in the polymer layer, it is easy to cause the luminescence reaction, and thus the detection accuracy of light can be increased. Therefore, even in the case of an expanded bead molding that exhibits black color, it is possible to sufficiently identify it by the luminescence reaction. Furthermore, by making the content of taggant particles in the foam layer 0 or lower than that of the polymer layer, it is possible to more reliably prevent the taggant particles from having an undesirable effect on the expanded state of the expanded beads.
[0107] From the viewpoint of increasing the degree of blackness and more sufficiently increasing the detection accuracy of the luminescent reaction, it is preferable to use expanded beads having the foamed layer and the polymer layer covering the foamed layer, and it is more preferable to use expanded beads having the foamed layer and the polymer layer covering the foamed layer, with the polymer layer located on the surface of the expanded beads.
[0108] [Method of manufacturing a thermoplastic polymer foamed bead molded product] The expanded bead molding of the present invention can be obtained by in-mold molding using the expanded beads of the present invention. For example, the expanded bead molding can be produced as follows. First, the expanded beads of the present invention are filled into a mold having a cavity corresponding to the shape of the desired expanded bead molding, and the expanded beads filled in the mold are heated by a heating medium such as steam. The expanded beads in the cavity are softened by heating, undergo secondary foaming, and the surfaces melt and fuse to each other. As a result, the expanded beads are integrated with each other, and an expanded bead molding corresponding to the shape of the cavity is obtained.
[0109] [Method for identifying expanded thermoplastic polymer beads or expanded thermoplastic polymer bead moldings] Next, the identification method of the present invention will be described. The identification method of the present invention includes the identification method of the thermoplastic polymer expanded beads of the present invention and the identification method of the thermoplastic polymer expanded bead molding of the present invention. Furthermore, the identification method of the present invention can identify the thermoplastic polymer expanded beads constituting the thermoplastic polymer expanded bead molding at the same time by identifying the thermoplastic polymer expanded bead molding. And, since the identification method of the present invention is non-destructive, it is possible to identify the expanded beads and the expanded bead molding while maintaining their beautiful appearance without changing the state of the expanded beads and the expanded bead molding before and after the identification process. The identification method of the present invention includes a first identification method including the configurations i) and ii) described below and further including at least iii-1), and a second identification method including the configurations i) and ii) described below and further including at least iii-2).
[0110] The first method for identifying expanded thermoplastic polymer beads of the present invention includes the following steps i) to iii-1). i) an electromagnetic wave irradiation step of irradiating the surface of the thermoplastic polymer foamed beads with electromagnetic waves; ii) a detection step of detecting a luminescence reaction caused by the luminescent rare earth element by the electromagnetic wave irradiation with a detection device to obtain an emission spectrum; iii-1) A discrimination step of comparing the emission spectrum with a blank spectrum that does not show a luminescence reaction derived from a luminescent rare earth element.
[0111] The first method for identifying an expanded thermoplastic polymer bead molding of the present invention includes the following steps i) to iii-1). i) an electromagnetic wave irradiation step of irradiating the surface of a thermoplastic polymer foamed bead molding with electromagnetic waves; ii) a detection step of detecting a luminescence reaction caused by the luminescent rare earth element by the electromagnetic wave irradiation with a detection device to obtain an emission spectrum; iii-1) A discrimination step of comparing the emission spectrum with a blank spectrum that does not show a luminescence reaction derived from a luminescent rare earth element.
[0112] According to the above steps i) to iii-1), it is possible to determine whether or not the expanded beads or the expanded bead molding of the present invention exhibits a luminescent reaction. Whether or not the expanded beads or the expanded bead molding shows a luminous reaction can be determined by the following method. Incidentally, FIG. 6 is referred to for the emission spectrum (S) and spectrum (S0) described later. First, an expanded bead molding to be identified and a blank molding having the same composition as the aforementioned object to be identified except that it does not contain a luminous rare earth element component are prepared. The blank molding is preferably an expanded bead molding produced in the same manner as the aforementioned object to be identified except that it does not contain a luminous rare earth element component. Then, they are irradiated with electromagnetic waves of a predetermined wavelength, and the emission spectrum (S) of the expanded bead molding of the present invention and the spectrum (S0) of the blank expanded bead molding generated by the irradiation are detected. Next, for all peaks appearing in the emission spectrum (S), the respective wavelengths and the peak intensity I of the emission peak at each wavelength are confirmed. Also, the intensity I0 of the spectrum (S0) at each wavelength confirmed as described above is confirmed. Then, the ratio (I / I0) of the peak intensity I at each wavelength in the emission spectrum (S) to the intensity I0 at each wavelength in the spectrum (S0) is calculated. In the following description, the ratio may be referred to as the ratio (I / I0) of peak intensities I, or simply as the ratio (I / I0). The maximum value of the ratios (I / I0) of the peak intensities I obtained at each wavelength is specified. The higher the maximum value of the ratio (I / I0), the more accurately the luminescence reaction of the expanded bead molding of the present invention is detected. When the maximum value of the ratio (I / I0) is 1.1 or more, it can be determined that a luminescence reaction has occurred in the object to be identified. On the other hand, when the maximum value of the ratio I / I0 is less than 1.0, or when no peak appears in the emission spectrum (S), it can be determined that no luminescence reaction has occurred. The ratio (I / I0) is preferably 1.3 or more, more preferably 1.5 or more, even more preferably 1.8 or more, and particularly preferably 2.0 or more. When the ratio (I / I0) is within the above range, it means that the luminescence reaction has occurred more efficiently and the detection accuracy has improved. However, the intensity I0 and the peak intensity I are measured under the same measurement conditions using the same device.
[0113] The above-mentioned discrimination can be performed by using expanded beads as the identification target instead of the expanded bead molding. In this case, the blank molding is preferably an expanded bead produced in the same manner as the expanded beads to be identified, except that it does not contain a luminescent rare earth element component.
[0114] The second method for identifying expanded thermoplastic polymer beads of the present invention includes the following steps i) to iii-2). i) an electromagnetic wave irradiation step of irradiating the surface of the thermoplastic polymer foamed particles with electromagnetic waves; ii) A detection step of detecting a luminescence reaction caused by the luminescent rare earth element due to the electromagnetic wave irradiation with a detection device to obtain an emission spectrum. iii-2) An identification step of comparing the emission spectrum with a preset reference emission spectrum showing a luminescence reaction originating from a luminescent rare earth element.
[0115] The second method for identifying an expanded thermoplastic polymer bead molding of the present invention includes the following steps i) to iii-2). i) an electromagnetic wave irradiation step of irradiating the surface of a thermoplastic polymer foamed bead molding with electromagnetic waves; ii) A detection step of detecting a luminescence reaction caused by the luminescent rare earth element due to the electromagnetic wave irradiation with a detection device to obtain an emission spectrum. iii-2) An identification step of comparing the emission spectrum with a preset reference emission spectrum showing a luminescence reaction originating from a luminescent rare earth element. The second identification method described above, including step iii-2), has a favorable effect in that it is possible to trace various information about the expanded beads, such as the properties of the material constituting the expanded beads, the physical properties of the expanded beads such as apparent density, production conditions such as production lot number and production date, and information on the origin of the manufacturer. The occurrence of this effect will be specifically described below.
[0116] In the second identification method of the present invention described above, the preset reference emission spectrum refers to an emission spectrum detected when an electromagnetic wave of a predetermined wavelength is irradiated to a molded article that contains a predetermined luminescent rare earth element component and is composed of a polymer of a predetermined composition, as described above. In other words, the reference emission spectrum is derived from a specific emission spectrum exhibited by the luminescent reaction of the predetermined luminescent rare earth element component. However, even when electromagnetic waves of the same wavelength are irradiated, the emission spectrum generated by the irradiation is influenced not only by the luminescent rare earth element component but also by the composition of the polymer constituting the expanded beads and any additives, so the reference emission spectrum is not necessarily the same as the inherent emission spectrum of the contained luminescent rare earth element component itself. Therefore, the preset reference emission spectrum is set so as to take into account the influence of the composition of the polymer constituting the expanded beads and additives.
[0117] In order to effectively utilize step iii-2), it is advisable to link various information, such as the properties of the constituent materials, the physical properties of the expanded beads such as apparent density, production conditions such as production lot number and production date, and information on the origin of the manufacturer, to the reference emission spectrum of the expanded beads. By carrying out the second identification method in this way, it is possible to trace the luminescent particles that show an emission spectrum with a similar pattern to the reference emission spectrum as being expanded particles having the same information as the reference expanded particles by the above-mentioned comparison. When the identification target is an expanded bead molding, it is possible to trace the expanded particles that constitute the expanded bead molding as being expanded particles having the same information as the reference expanded particles by the above-mentioned comparison. In other words, the second identification method including step iii-2) allows for more advanced identification.
[0118] The content of the luminescent rare earth element component such as taggant particles in the expanded beads used to obtain the reference emission spectrum is generally 0.0001% by mass or more and 0.5% by mass or less. When obtaining the preset reference emission spectrum, it is preferable to obtain the inherent emission spectrum of the luminescent rare earth element component itself as shown in FIG. 5. This makes it possible to compare the peak in the inherent emission spectrum of the luminescent rare earth element component itself with the peak of the preset reference emission spectrum. In this case, the accuracy of the identification process can be further improved. The emission spectrum of the expanded beads or expanded bead molding to be identified is confirmed in a chart in which the vertical axis indicates the peak intensity and the horizontal axis indicates the wavelength, as in the emission spectrum (S) in FIG. 6. The emission spectrum (S) of the expanded beads or expanded bead molding containing a luminescent rare earth element component is judged to have a pattern similar to that of a reference emission spectrum (not shown) based on the concept of emission peaks consisting of elements such as the shape of the entire pattern, the number of peaks, the wavelength at which each peak is detected, the shape of each peak, the intensity ratio between each peak, and the area ratio between each peak. The absolute value of the peak intensity does not need to be included in the elements that make up the emission spectrum. However, the reference emission spectrum and the emission spectrum to be identified are measured using the same device under the same measurement conditions.
[0119] Even if the details of the luminescent rare earth element component contained in the taggant particle are unknown, the above-mentioned detection and matching are possible and the expanded beads or expanded bead moldings to be identified can be identified by irradiating an electromagnetic wave of a predetermined wavelength to an expanded bead of a predetermined composition containing the taggant particle, so long as a reference expansion spectrum has been confirmed in advance. Note that details of the luminescent rare earth element component refer to, for example, the type and combination of luminescent rare earth elements contained in the luminescent rare earth element component, the type of ligand that coordinates the luminescent rare earth element, the production method thereof, etc.
[0120] The specific means for matching the reference emission spectrum with the detected emission spectrum is not particularly limited. For example, a detection device equipped with a program that calculates the degree to which the detected emission spectrum statistically matches the reference emission spectrum and automatically judges the matching result from the degree of match can be used. In addition, for example, the number and wavelength of peaks shown in the pattern of the reference emission spectrum and peaks shown in the detected emission spectrum can be compared, and when two or more peaks are shown, the comparison can also be performed manually by comparing the area ratio of each peak.
[0121] The marking methods of the prior art such as those disclosed in Patent Documents 1 and 2 can be easily identified by visually observing the surface of the molded product, but there is a risk of the molded product being copied by a malicious third party. According to the present invention, the emission spectrum pattern can be finely adjusted, for example, by the type and combination of the selected luminescent rare earth elements and the type of ligand that coordinates the luminescent rare earth elements. Therefore, the marking by the emission spectrum is prevented from being copied by a third party. In addition, the authenticity can be easily determined by defining the reference spectrum as the emission spectrum of the genuine product and comparing it with the emission spectrum detected from the expanded beads or expanded bead moldings to be identified. EXAMPLES
[0122] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. Table 1 shows details of the resins used in the examples and comparative examples. Tables 2 to 4 show the compositions and contents for producing the expanded beads of each example and each comparative example, and also show the evaluation results of each example and each comparative example. In the tables, carbon black is represented as CB. The content of each component here is the same as the blending amount of each component blended to produce the expanded beads. In the examples and comparative examples shown below, resin particles were produced using a resin material as the thermoplastic polymer particles.
[0123] The luminescent compounds used in the examples and comparative examples are as follows: Luminescent compound 1 is a taggant particle containing a luminescent rare earth element, and luminescent compound 2 and luminescent compound 3 are granular luminescent compounds not containing a luminescent rare earth element. FIG. 5 shows a chart of the emission spectrum detected when the luminescent compound 1 was irradiated with ultraviolet light having a wavelength of 320 nm. <Light-emitting compound 1> Manufactured by OLNICA; Grade name OLNICA65013919 (crystalline ligand obtained by reacting luminescent rare earth elements with unsaturated organic ligands) Luminescent rare earth elements contained: Terbium Electromagnetic waves used: 320nm ultraviolet light The specific emission spectrum of the luminescent compound 1 shows peaks at 488 nm, 546 nm, 589 nm, and 622 nm. <Light-emitting compound 2> Manufactured by Sigma-Aldrich; 4,4-bis(2-benzoxazolyl)stilbene(BBS) Electromagnetic waves used: 320nm ultraviolet light The specific emission spectrum of the luminescent compound 2 shows peaks at 430 nm, 470 nm, and 500 nm. <Light-emitting compound 3> Quinacridone-based organic color pigments Electromagnetic waves used: 320nm ultraviolet light Intrinsic emission spectrum of luminescent compound 3; 653 nm
[0124] In advance, the expanded beads containing each luminescent compound and having the same composition as each Example and Comparative Example were irradiated with ultraviolet light having a wavelength of 320 nm, and the emission spectrum of the resulting luminescent reaction was detected with a detection device described later to confirm the reference emission spectrum. These reference emission spectra are not required in the detection test of the luminescent reaction described later. As described at the end of this Example, the reference emission spectrum is used when comparing the reference emission spectrum with the emission spectrum of each Example and Comparative Example when implementing the second identification method of the present invention.
[0125] <Example 1> (Preparation of resin particles) A manufacturing apparatus was prepared, which was equipped with a core layer forming extruder with an inner diameter of 50 mm, a multilayer strand forming die attached to the downstream side of the core layer forming extruder, and a coating layer forming extruder with an inner diameter of 30 mm. The manufacturing apparatus was configured so that the downstream side of the coating layer forming extruder and the multilayer strand forming die were connected, and the melt-kneaded materials for forming each layer in the die could be stacked and co-extruded. As the resin constituting the core layer, a virgin polypropylene-based resin (PP1) having a melting point of 144°C and a melt mass flow rate of 5g / 10 minutes was used. As the core layer molding material constituting the core layer, in addition to the above-mentioned resin, zinc borate was used as a bubble adjuster so as to be 0.1 parts by mass relative to 100 parts by mass of the core layer molding material, and carbon black was used in the amounts shown in Table 2, and these were supplied to the core layer forming extruder and melt-kneaded. As the resin constituting the coating layer, a virgin polypropylene-based resin (PP2) having a melting point of 134° C. and a melt mass flow rate of 5 g / 10 min was used. As the coating layer forming material constituting the coating layer, in addition to the above-mentioned resin, luminescent compound 1 and carbon black were used in the amounts shown in Table 2, and these were fed to a coating layer forming extruder and melt-kneaded. The molten mixtures for forming each layer obtained by melt kneading as described above were introduced into a die for forming a multilayer strand and merged in the die, and a multilayer strand having a two-layer structure (coating layer / core layer) having a core layer and a coating layer coating the lateral surface of the core layer was extruded from the fine holes in the die attached to the downstream side of the die. The extruded strand was water-cooled in a water tank and cut with a pelletizer to obtain resin particles with an average mass of 1.0 mg per piece.
[0126] (Preparation of expanded beads) 1 kg of the resin particles obtained as described above was supplied together with 3 L of water as an aqueous dispersion medium into a pressure vessel having a capacity of 5 L. In addition, 0.3 parts by mass of kaolin as an inorganic dispersant and 0.004 parts by mass (as an active ingredient) of a surfactant (product name: NEOGEN, manufactured by Daiichi Kogyo Seiyaku Co., Ltd., sodium dodecylbenzenesulfonate) were added to the pressure vessel relative to 100 parts by mass of the resin particles. Next, carbon dioxide was injected as a blowing agent into the pressure vessel, and the pressure was increased to a gauge pressure of 2.0 MPa (G). Note that the pressures marked with (G) are gauge pressures, that is, pressure values based on atmospheric pressure. Thereafter, the pressure vessel was heated at a rate of 2°C / min while stirring to the foaming temperature shown in Table 2, and the temperature was maintained for 15 minutes. This was adjusted so that a high-temperature peak would appear on the endothermic curve of the resulting expanded beads measured by DSC. Thereafter, the resin particles and water contained in the pressure vessel were released under atmospheric pressure to expand the core layer, thereby obtaining expanded beads having a multi-layer structure including a foamed layer and a non-foamed coating layer, which is a polymer layer, and the coating layer covers the foamed layer. The expansion pressure in the pressure vessel immediately before expansion was the value shown in Table 2. The obtained expanded beads were left to cure for 24 hours in an environment of 23°C, relative humidity 50%, and 1 atm.
[0127] (Production of foamed bead moldings) The cured expanded beads were packed by compression filling into a mold (specifically, a metal mold) having a molding cavity capable of molding a flat-shaped molded body of 400 mm long x 300 mm wide x 30 mm high, at a packing rate P shown in Table 2. Compression filling is a filling method in which the expanded beads are packed into the mold while being pressurized. Then, steam was supplied into the mold to heat the expanded beads, thereby obtaining a flat-shaped expanded bead molded body. Heating with steam was performed as follows. First, steam was supplied to the mold while the drain valves provided on both sides of the mold were opened, to perform preheating (exhaust process). Then, steam was supplied from one side of the mold to heat it, and steam was further supplied from the other side of the mold to heat it. Next, steam was supplied from both sides of the mold to heat it until the inside of the mold reached the molding pressure listed in Table 2. After heating, the pressure was released, and the mold was cooled with water until the pressure generated on the molding surface of the mold was 0.04 MPa (G), after which the mold was opened and the expanded bead molded body was taken out. The obtained expanded bead molding was cured in an oven at 80° C. for 12 hours, and then slowly cooled to room temperature to obtain an expanded bead molding.
[0128] The filling rate P is a value expressed by the following formula (1). [Formula 1] P = [a / (b × c)] × 100 (1) (wherein, a in the formula (1) is the mass (unit: kg) of the expanded beads filled in the mold, and b is the bulk density (unit: kg / m 3 ), and c is the internal volume of the mold (unit: m 3 )
[0129] <Examples 2, 3, 7 to 11, Example 14 and Comparative Example 1> Except for the changes shown in Tables 2 to 4, the expanded beads and expanded bead moldings were produced in the same manner as in Example 1.
[0130] <Examples 4 to 6, 12, and 13 and Comparative Examples 2 and 3> The resins, carbon black, and luminescent compounds shown in Tables 2 to 4 were melt-kneaded to prepare melt-kneaded products. The melt-kneaded products were then fed into a single-layer extruder to extrude strands. The extruded strands were cooled with water and cut with a pelletizer to obtain resin particles with an average mass of 1.0 mg per piece.
[0131] The resin particles obtained as described above were expanded in the same manner as in Example 1 to produce single-layer expanded particles.
[0132] An expanded bead molding was produced in the same manner as in Example 1 using the expanded beads obtained as described above.
[0133] <Measurement of bulk density of expanded beads> The expanded particles were conditioned by leaving them to stand for 24 hours in an environment of 23°C temperature, 50% relative humidity, and 1 atm. After conditioning, the expanded particles with mass W (g) were filled into a measuring cylinder so that they would naturally pile up, and the filling height of the expanded particles in the measuring cylinder was stabilized by tapping the bottom of the measuring cylinder lightly against a horizontal surface several times. The bulk volume V (L) of the expanded particles indicated by the graduations on the measuring cylinder was read, and the mass W of the expanded particles was divided by the bulk volume V of the expanded particles (W / V), and the bulk density of the expanded particles (kg / m) was calculated by converting the unit. 3 ) was obtained.
[0134] <Measurement of the heat of fusion of the high-temperature peak of expanded beads> According to JIS K7122-1987, a 2 mg test piece of foamed beads was heated and melted at a heating rate of 10°C / min from 30°C to a temperature 30°C higher than the end of the melting peak, and a first DSC curve (see FIG. 7) was obtained. A straight line was drawn connecting point I, which corresponds to 80° C. on the DSC curve, and point II, which corresponds to the end temperature of melting of the expanded beads, on the DSC curve shown in Fig. 7. The end temperature of melting is the high-temperature end point of high-temperature peak b, and is the intersection point of high-temperature peak b and the baseline on the higher temperature side of high-temperature peak b on the DSC curve. As shown in Figure 7, after drawing a line connecting points I and II, the intersection point of the line passing through the maximum point III between the intrinsic peak a and the high-temperature peak b and parallel to the vertical axis of the graph with the line connecting points I and II was designated as IV. The area of the portion surrounded by the straight line connecting points I and IV, the straight line connecting points III and IV, and the DSC curve connecting points I and III was defined as the area of intrinsic peak a. The area of the portion surrounded by the straight line connecting points IV and II, the straight line connecting points III and IV, and the DSC curve connecting points III and II (shaded portion) was defined as the area of high-temperature peak b. The value of the total heat of fusion of the expanded beads was calculated from the sum of the areas of intrinsic peak a and high-temperature peak b obtained as described above, and the value of the heat of fusion of high-temperature peak b was calculated from the area of high-temperature peak b.
[0135] <Measurement of the average bubble diameter of expanded beads and calculation of the rate of variation of the bubble diameter> First, the expanded beads were cut into two equal parts. Next, a photograph of the cross section was taken so that the exposed cut surface was entirely within the field of view. On the photograph, four lines were drawn from the outermost surface of the expanded beads through the center to the outermost surface on the opposite side, with the angle between adjacent lines being equal. In other words, on the photograph, four lines were drawn such that the angle between adjacent lines was 45°. The total length L of the four lines thus obtained was divided by the number N of all the bubbles in contact with the lines, and the value (L / N) was taken as the average bubble diameter of one expanded bead. This operation was performed on 20 expanded beads, and the arithmetic average value was taken as the average bubble diameter of the expanded beads. The standard deviation of the cell diameters of the expanded beads was divided by the average cell diameter of the expanded beads and the result was multiplied by 100 to obtain the coefficient of variation. The value given by the square root of the unbiased variance was taken as the standard deviation.
[0136] <Measurement of Molded Body Density of Expanded Bead Molded Body> The mass was calculated by dividing the mass of the expanded bead molding by the volume calculated based on the dimensions.
[0137] <Measurement of L* value of expanded bead molding> Five sites were randomly selected from the skin surface of the expanded bead molding, i.e., the surface that was in contact with the mold during in-mold molding, and the L* value of the expanded bead molding was measured using a spectrophotometer ("SE2000" manufactured by Nippon Denshoku Industries Co., Ltd.). The measurement range was 30 mmφ, and the measurement method was the reflection method. The arithmetic average value of the L* values at these five measurement positions was taken as the L* value of the expanded bead molding.
[0138] <Luminescence reaction detection test> In the detection test, a luminescence reaction detection test from the foamed bead molding was carried out using a spectrometer (product name: AvaSpec-2048) manufactured by AVANTES as a detection device for the luminescence reaction. The detection device has at least a function of detecting the emission spectrum of the luminescence reaction caused by the irradiation of the electromagnetic waves. Specifically, a test piece was cut out from the expanded bead molding so that the skin surface was the detection target surface, and was placed in the holder of the detection device. Then, the detection target surface was irradiated with ultraviolet light having a wavelength of 320 nm using an ultraviolet irradiation device. Then, the emission spectrum (S) emitted from the expanded bead molding by such irradiation was detected. In addition, for each peak in the emission spectrum (S), the wavelength at which each peak was confirmed and the peak intensity I of each peak were recorded. The emission spectrum (S) in Example 1 is shown in FIG. 6.
[0139] (Ratio of peak intensity I (I / I0)) Except for not blending the luminescent compound, the expanded beads were produced in the same manner as in each Example and Comparative Example, and the expanded beads were used to produce a blank expanded bead molding. The blank expanded bead molding was used to perform detection in the same manner as in the luminescence reaction detection test, and the spectrum (S0) emitted from the blank expanded bead molding was detected. Since the blank expanded bead molding does not contain a luminescent compound, the spectrum (S0) can also be called a "baseline" that does not show a clear emission peak. The blank spectrum (S0) in Example 1 is shown in FIG. 6. The intensity I0 of the spectrum (S0) at each wavelength confirmed as described above in the emission spectrum (S) was confirmed. Then, the ratio (I / I0) of the peak intensity I at each wavelength in the emission spectrum (S) to the intensity I0 at each wavelength in the spectrum (S0) was calculated. Then, the maximum value of the obtained ratios (I / I0) of the peak intensities I was specified. This was taken as the maximum value of the ratios (I / I0) of the peak intensities I, and is shown in Tables 2 to 4. When the maximum value of the ratios (I / I0) of the peak intensities I was 1.1 or more, it was determined that the expanded beads constituting the expanded bead molding exhibited a luminescence reaction. In addition, the higher the maximum value of the ratios (I / I0) of the peak intensities I, the more accurately the luminescence reaction could be detected. As shown in Tables 2 to 4, the maximum value of the ratio of peak intensity I (I / I0) was 1.1 or more in all the examples, and it was confirmed that the expanded beads of the present invention could be identified as the expanded beads of the present invention by detecting a luminescence reaction derived from a luminescent rare earth element upon irradiation with electromagnetic waves. Note that in all the examples using the luminescent compound 1, the wavelength of the emission peak of the emission spectrum (S) showing the maximum value of the ratio of peak intensity I (I / I0) was 546 nm.
[0140] In this embodiment, the detection test of the luminescence reaction was carried out based on the first identification method, but this test does not limit the method of identifying the expanded beads of the present invention. For example, using expanded beads or expanded bead moldings containing one or more predetermined luminescent rare earth element components, a preset reference emission spectrum is confirmed. Then, a second identification method can be adopted to identify the object to be identified by comparing the emission spectrum of the expanded beads or expanded bead moldings to be identified with the preset reference emission spectrum. The collation may be performed by a program that judges whether the patterns of both emission spectra match by comparing one or more items selected from the number of peaks in both emission spectra to be collated, the wavelengths of the peaks, the intensity ratio between the peaks, the area ratio between the peaks, etc. By employing such an identification method, it becomes possible to identify expanded beads or expanded bead moldings at a higher level.
[0141] For example, a more advanced identification of expanded beads or expanded bead moldings by the second identification method can be performed as follows. First, expanded beads (No. 1) containing luminescent compound 1 are produced using recycled raw materials as the polypropylene-based resin. Next, the expanded beads (No. 1) are molded in a mold to produce expanded bead moldings (No. 1). The expanded beads (No. 1) and expanded bead moldings (No. 1) can be produced by the same method as in Example 1, except that recycled raw materials are used as the polypropylene-based resin. A test piece is cut out from the foamed bead molding (No. 1) so that the skin surface is the detection target surface, and ultraviolet light with a wavelength of 320 nm is irradiated onto the detection target surface. The emission spectrum emitted from the foamed bead molding (No. 1) by such irradiation is detected, and the foam spectrum is recorded in the device as a reference emission spectrum. The reference emission spectrum is then linked to information that the foamed bead molding is made of foamed beads manufactured using recycled polypropylene resin. Next, expanded beads (No. 2) containing the luminescent compound 1 are manufactured using recycled raw materials as polypropylene-based resin. The expanded beads (No. 2) are then molded in a mold to manufacture the expanded bead molding (No. 2) to be identified. The expanded beads (No. 2) and the expanded bead molding (No. 2) are manufactured, for example, by the same method as in Example 1. Then, the emission spectrum emitted from the expanded bead molding (No. 2) by such irradiation is detected, and the expansion spectrum is compared with the reference emission spectrum detected as described above to confirm that the patterns of both emission spectra match. If the above operations result in a match between the two emission spectral patterns, the expanded bead molding (No. 2) to be identified is identified as an expanded bead molding made of expanded beads produced using the recycled polypropylene resin, similar to the expanded beads (No. 1).
[0142] [Table 1]
[0143] [Table 2]
[0144] [Table 3]
[0145] [Table 4]
[0146] The present invention described above encompasses the following technical ideas. (1) Thermoplastic polymer foam particles that exhibit a luminescent reaction due to luminescent rare earth elements when exposed to electromagnetic waves. (2) The thermoplastic polymer foamed particles according to (1) above, which contain taggant particles constituted by using the luminescent rare earth element. (3) The expanded thermoplastic polymer beads according to (2) above, wherein the taggant particle content Ctt in the expanded thermoplastic polymer beads is 0.0001% by mass or more and 0.5% by mass or less. (4) The thermoplastic polymer foamed particles have a foamed layer made of a thermoplastic polymer and a polymer layer made of a polymer, The thermoplastic polymer foamed beads according to (3), wherein the ratio [Ctr / Ctt] of the taggant particle content Ctr in the polymer layer to the taggant particle content Ctt in the thermoplastic polymer foamed beads is 2 or more. (5) The thermoplastic polymer expanded bead according to (4) above, wherein the polymer layer is located on the surface of the expanded bead. (6) The expanded thermoplastic polymer beads according to (4) or (5) above, wherein the content Ctr of the taggant particles in the polymer layer is 0.001% by mass or more and 5% by mass or less. (7) The expanded thermoplastic polymer beads according to any one of (4) to (6), which have a multilayer structure composed of the expanded layer and the polymer layer covering 50% or more of the surface area of the expanded thermoplastic polymer beads. (8) The thermoplastic polymer foamed particles have a foamed layer made of a polyolefin-based resin and a polymer layer made of a polyolefin-based resin, The thermoplastic polymer foamed particles according to any one of (1) to (7), wherein the difference [Tmc-Tms] between the melting point Tmc of the polyolefin resin constituting the foamed layer and the melting point Tms of the polyolefin resin constituting the polymer layer is 3°C or more and 35°C or less. (9) The thermoplastic polymer expanded beads according to any one of (1) to (8), wherein the thermoplastic polymer expanded beads contain carbon particles, and the carbon particle content Cct in the thermoplastic polymer expanded beads is 0.01 mass% or more and 15 mass% or less. (10) The expanded thermoplastic polymer particles according to any one of (1) to (9) above, wherein the expanded thermoplastic polymer particles are made of a polyolefin resin. (11) The expanded thermoplastic polymer particles according to any one of (1) to (10) above, wherein the expanded thermoplastic polymer particles contain a recycled thermoplastic polymer. (12) The thermoplastic polymer foamed particles according to any one of (1) to (11), wherein the luminescent reaction is derived from one or more luminescent rare earth elements selected from the group consisting of praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), and thulium (Tm). (13) The expanded thermoplastic polymer beads according to any one of (1) to (12), wherein the average bubble diameter of the expanded thermoplastic polymer beads is 30 μm or more and 200 μm or less, and the coefficient of variation of the bubble diameter is 25% or less. (14) The expanded thermoplastic polymer beads according to any one of (1) to (13), wherein the carbon particle content Cct in the expanded thermoplastic polymer beads is 0.01% by mass or more and 15% by mass or less, the average bubble diameter of the expanded thermoplastic polymer beads is 30 μm or more and 200 μm or less, and the coefficient of variation of the bubble diameter is 25% or less. (15) A thermoplastic polymer expanded bead molding obtained by molding the thermoplastic polymer expanded bead according to any one of (1) to (14) above in a mold. (16) A method for identifying a thermoplastic polymer foamed bead according to any one of (1) to (15) or a thermoplastic polymer foamed bead molded product obtained by molding the thermoplastic polymer foamed bead in a mold, comprising the steps of: i) an electromagnetic wave irradiation step of irradiating the surface of a thermoplastic polymer foamed bead or a thermoplastic polymer foamed bead molding with electromagnetic waves; ii) a detection step of detecting a luminescence reaction caused by the luminescent rare earth element by the electromagnetic wave irradiation with a detection device to obtain an emission spectrum; and iii) at least one identification step selected from the following iii-1) and iii-2): iii-1) A discrimination step of comparing the emission spectrum with a blank spectrum that does not show a luminescence reaction derived from a luminescent rare earth element. iii-2) An identification step of comparing the emission spectrum with a preset reference emission spectrum showing a luminescence reaction originating from a luminescent rare earth element. (17) Expanded beads comprising a thermoplastic polymer and a luminescent rare earth element component that emits light and exhibits a specific emission spectrum when irradiated with electromagnetic waves, The emission spectrum detected by irradiating the expanded beads with the electromagnetic wave is compared with a preset reference emission spectrum showing a light emission reaction derived from a luminescent rare earth element, Expanded thermoplastic polymer beads, characterized in that they are identifiable as expanded beads containing the luminescent rare earth element. (18) Expanded beads made of a thermoplastic polymer, i) an electromagnetic wave irradiation step of irradiating the surface of the expanded beads with electromagnetic waves; ii) a detection step of detecting a luminescence reaction caused by the luminescent rare earth element by the electromagnetic wave irradiation with a detection device to obtain an emission spectrum; iii-2) an identification step of comparing the emission spectrum with a preset reference emission spectrum showing a luminescence reaction originating from a luminescent rare earth element, A thermoplastic polymer foam particle that can be identified as a foam particle containing a luminescent rare earth element. (19) Expanded beads made of a thermoplastic polymer, i) an electromagnetic wave irradiation step of irradiating the surface of the expanded beads with electromagnetic waves; ii) a detection step of detecting a luminescence reaction caused by the luminescent rare earth element by the electromagnetic wave irradiation with a detection device to obtain an emission spectrum; iii-2) an identification step of comparing the emission spectrum with a preset reference emission spectrum showing a luminescence reaction originating from a luminescent rare earth element, 1. A thermoplastic polymer foam particle characterized in that it is identified as being a foam particle containing a luminescent rare earth element. (20) A foamed bead molding obtained by molding foamed beads containing a thermoplastic polymer and a luminescent rare earth element component that emits light and exhibits a specific emission spectrum when irradiated with electromagnetic waves, The emission spectrum detected by irradiating the expanded bead molding with the electromagnetic wave is compared with a preset reference emission spectrum showing a light emission reaction originating from a luminescent rare earth element, 3. A thermoplastic polymer foamed bead molding, which can be identified as being made from foamed beads containing the luminescent rare earth element. (21) A foamed bead molding obtained by molding foamed beads made of a thermoplastic polymer in a mold, i) an electromagnetic wave irradiation step of irradiating the surface of the foamed bead molding with electromagnetic waves; ii) a detection step of detecting a luminescence reaction caused by the luminescent rare earth element by the electromagnetic wave irradiation with a detection device to obtain an emission spectrum; iii-2) an identification step of comparing the emission spectrum with a preset reference emission spectrum showing a luminescence reaction originating from a luminescent rare earth element, 1. A thermoplastic polymer foamed bead molding, which can be identified as being made of foamed beads containing a luminescent rare earth element. (22) A foamed bead molding obtained by molding foamed beads made of a thermoplastic polymer in a mold, i) an electromagnetic wave irradiation step of irradiating the surface of the foamed bead molding with electromagnetic waves; ii) a detection step of detecting a luminescence reaction caused by the luminescent rare earth element by the electromagnetic wave irradiation with a detection device to obtain an emission spectrum; iii-2) an identification step of comparing the emission spectrum with a preset reference emission spectrum showing a luminescence reaction originating from a luminescent rare earth element, 1. A thermoplastic polymer foamed bead molding, characterized in that it is identified as being an expanded bead molding made of expanded beads containing a luminescent rare earth element. [Explanation of symbols]
[0147] 10 Taggant particles 20...Foam layer 21...end face 30...Polymer layer 40...Top surface layer 100, 100A, 100B, 100C, 100D... Foam particles d1...area S: A chart showing an emission spectrum of the expanded bead molding of Example 1. S0: A chart showing the spectrum of the blank expanded bead molding of Example 1.
Claims
1. Thermoplastic polymer foam particles that exhibit a luminescent reaction due to luminescent rare earth elements when irradiated with electromagnetic waves.
2. 2. The thermoplastic polymer foam particles of claim 1, wherein said thermoplastic polymer foam particles contain taggant particles containing said luminescent rare earth element.
3. The expanded thermoplastic polymer beads according to claim 2, wherein the content Ctt of the taggant particles in the expanded thermoplastic polymer beads is 0.0001% by mass or more and 0.5% by mass or less.
4. The thermoplastic polymer foamed particles have a foamed layer made of a thermoplastic polymer and a polymer layer made of a polymer, The thermoplastic polymer foamed beads according to claim 3, wherein the ratio [Ctr / Ctt] of the taggant particle content Ctr in the polymer layer to the taggant particle content Ctt in the thermoplastic polymer foamed beads is 2 or more.
5. The thermoplastic polymeric foam bead of claim 4 , wherein the polymer layer is located on a surface of the foam bead.
6. The expanded thermoplastic polymer beads according to claim 4 or 5, wherein the content Ctr of the taggant particles in the polymer layer is 0.001% by mass or more and 5% by mass or less.
7. The thermoplastic polymer foamed beads according to claim 4 or 5, having a multilayer structure constituted by the foamed layer and the polymer layer covering 50% or more of the surface area of the foamed layer.
8. The thermoplastic polymer foamed particles have a foamed layer made of a polyolefin-based resin and a polymer layer made of a polyolefin-based resin, The thermoplastic polymer foam particles according to claim 4 or 5, wherein the difference [Tmc-Tms] between the melting point Tmc of the polyolefin resin constituting the foam layer and the melting point Tms of the polyolefin resin constituting the polymer layer is 3°C or more and 35°C or less.
9. The thermoplastic polymer foamed beads according to claim 1 or 2, wherein the thermoplastic polymer foamed beads contain carbon particles, and the carbon particle content Cct in the thermoplastic polymer foamed beads is 0.01 mass% or more and 15 mass% or less.
10. 3. The expanded thermoplastic polymer beads according to claim 1 or 2, wherein the expanded thermoplastic polymer beads are made of a polyolefin resin.
11. 3. The thermoplastic polymer foam particles according to claim 1 or 2, wherein the thermoplastic polymer foam particles comprise a recycled thermoplastic polymer.
12. 3. The thermoplastic polymer foam particles according to claim 1 or 2, wherein the luminescent reaction is derived from one or more luminescent rare earth elements selected from the group consisting of praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), and thulium (Tm).
13. 3. The expanded thermoplastic polymer beads according to claim 1, wherein the average cell diameter of the expanded thermoplastic polymer beads is 30 μm or more and 200 μm or less, and the coefficient of variation of the cell diameter is 25% or less.
14. 6. A thermoplastic polymer expanded bead molding obtained by molding the thermoplastic polymer expanded bead according to claim 1 in a mold.
15. A method for identifying the expanded thermoplastic polymer beads according to any one of claims 1 to 5 or a thermoplastic polymer expanded bead molding obtained by molding the expanded thermoplastic polymer beads in a mold, comprising the steps of: i) an electromagnetic wave irradiation step of irradiating the surface of a thermoplastic polymer foamed bead or a thermoplastic polymer foamed bead molding with electromagnetic waves; ii) a detection step of detecting a luminescence reaction caused by the luminescent rare earth element by the electromagnetic wave irradiation with a detection device to obtain an emission spectrum; and A method for identifying expanded thermoplastic polymer beads or expanded thermoplastic polymer bead moldings, comprising: iii) at least one identification step selected from the following iii-1) and iii-2). iii-1) A discrimination step of comparing the emission spectrum with a blank spectrum that does not show a luminescence reaction derived from a luminescent rare earth element. iii-2) An identification step of comparing the emission spectrum with a preset reference emission spectrum showing a luminescence reaction originating from a luminescent rare earth element.
Citation Information
Patent Citations
Foamed resin molding raw material packing machine and mold using the raw material packing machine
JP2010149297A
Molded article, production method for laser-marked molded article, and laser marking method
WO2022191310A1
Cited By
Device for collecting a biological sample
US12376837B2
Device for collecting a biological sample
US12558075B2